Artificial intelligence-assisted phenotypic monitoring and diagnostic of wastewater microbiome management towards sustainability - Zijian Wang; Yuan Yan; IL Han; Jangho Lee; Guangyu Li; Peisheng He; Annalisa Onnis-Hayden; Nicholas B. Tooker; Zijun Meng; Mark Wallace Miller; Kester McCullough; Stephanie Klaus; et al. (Water Research, 2026)

Economic analysis and optimization of renewable natural gas production from prairie biomass - Elmin Rahic; Nicholas Cassady; Cooper Hess; Mark Mba-Wright; Zhiyou Wen; Juliana Vasco-Correa (Bioresource Technology, 2026)

Examining widely held propositions on human dietary protein needs and benefits: a critical review of the science that shapes both the data and our understanding of an essential macronutrient - Mitchell M. Kanter; Sally Aaron; Steven N. Austad; Andrew W. Brown; Nicholas A. Burd; Wayne W. Campbell; Mark Cope; Teresa A. Davis; John W. Erdman; Miguel Freitas; Kristen Hicks-Roof; Samuel Klein; et al. (Critical Reviews in Food Science and Nutrition, 2026)

From Hazard Occurrence to Risk Assessment: Antimicrobial Resistance and Chemical Co-selection in Ready-to-Eat Vegetables: A Scoping Review - Jowenna X.F. Sim; Claire Hayward; Mark Drew; Fran Lopez-Ruiz; Sukhvinder Pal Singh; Nicholas J. Ashbolt; Barbara Drigo (Trends in Food Science & Technology, 2026)

Yersinia pseudotuberculosis infection in four free-ranging odontocetes - Nicholas J. Davison; Stephen A. Raverty; Els M. Broens; Andrew C. Brownlow; Mark P. Dagleish; Andrea Gröne; Marja J.L. Kik; Linde van Schalkwijk; Lonneke L. IJsseldijk (Journal of Comparative Pathology, 2026)

Exploring trip preference heterogeneity in away-from-home birdwatchers using a discrete choice experiment - Katherine A. Sainsbury; Howard W. Harshaw; Nicholas W. Cole; Mark P. Vrtiska; David C. Fulton; Andrew H. Raedeke; Ashley A. Dayer; Jennie N. Duberstein; Rudy M. Schuster (Journal of Outdoor Recreation and Tourism, 2026)

Critical habitats for sharks and rays in Asia remain largely unprotected - Adriana Gonzalez-Pestana; Peter M. Kyne; Emiliano García-Rodríguez; Ryan Charles; Vanessa Bettcher Brito; Asia O. Armstrong; Amanda Batlle-Morera; Marta D. Palacios; Christoph A. Rohner; Giuseppe Notarbartolo di Sciara; Jo Marie V. Acebes; Serena Adam; et al. (Biodiversity and Conservation, 2026)
The Asia region harbors exceptional chondrichthyan (shark, ray, and chimaera) diversity but faces intense fishing pressure. The Important Shark and Ray Areas (ISRA) process provides a collaborative, evidence-based framework to identify critical habitats and inform spatial management. We assessed ISRAs across the Bay of Bengal, Southeast Asia, and the Northwest Pacific to characterize their extent, ecological significance, and conservation relevance. We delineated 122 ISRAs spanning ~ 1 million km 2 (~ 3% of the region) across 12 jurisdictions and international waters, encompassing habitats for 121 species (~ 30% of Asia’s chondrichthyans), 76% of which are threatened. Depleted taxa (e.g., giant guitarfishes, Glaucostegidae) were represented, but charismatic megafauna (e.g., Whale Shark Rhincodon typus ) were overrepresented. In contrast, deepwater and freshwater species were underrepresented. Reproductive Areas were the most common ISRA sub-criterion applied (52% of ISRAs), largely in nearshore zones, while areas for range-restricted species were less frequently (18%) identified. Twelve ISRAs overlapped with biodiversity hotspots, including seven in areas of high overall chondrichthyan species richness and five in areas of high range-restricted species richness. Citizen science was the predominant research method used to delineate ISRAs, while fisheries data were underused despite the region’s major fisheries footprint. Geographic coverage was uneven: Indonesia held the most ISRAs (n = 40; 71.7% of ISRA coverage) while eight jurisdictions (e.g., Viet Nam, China, Republic of Korea) lacked ISRAs due to data gaps. Protection shortfalls are stark: MPAs cover

Methods for investigating trace metal speciation and partitioning in mangrove sediments: a systematic quantitative literature review - Mark J. Donaldson; Nicholas J. C. Doriean; William W. Bennett (Journal of Soils and Sediments, 2026)
Purpose Mangrove rhizosphere sediments are strong sinks for trace metals, yet conventional sampling and analytical approaches often lack the resolution to capture the fine-scale biogeochemical processes driving metal immobilisation. This review evaluates the limitations of common methodologies used to study trace metal speciation and partitioning in mangrove sediments and provides recommendations for best practices. Methods A systematic quantitative literature review was conducted on peer-reviewed articles published between 1991 and 2026. Searches across four databases yielded 667 articles, of which 187 met the selection criteria and were coded to evaluate global methodological trends and identify key limitations and opportunities for improvement. Results Most studies were conducted in Asia, followed by Brazil and Australia, with Avicennia marina the most frequently studied species. The most frequently reported metals were Cu, Zn, Pb, Fe, Ni, Cr, Cd, and Mn, reflecting industrial relevance and toxicity. Sequential extraction methods were applied in 45% of studies; however, anoxic sample handling, critical for preserving redox-sensitive phases, was rarely reported. High-resolution techniques such as DGT and DET were seldom used despite their capacity to resolve fine-scale biogeochemical processes. Conclusion Conventional sampling and analytical approaches often fail to capture the fine-scale, redox-driven processes driving trace metal sequestration and partitioning in mangrove sediments. Adoption of methods to preserve in-situ redox conditions and the application of high-resolution analytical approaches to study fine-scale biogeochemical processes will enhance our understanding of trace metal mobility and ecological risk in mangrove ecosystems.

Diversity and functional group composition drive biogeographic patterns in marine biogenic structural complexity - Dean S. Janiak; Matthew A. Whalen; David R. Branson; Soledad Álvarez; Gail V. Ashton; Nicholas M. Bartkowiak; Simon J. Brandl; João Canning‐Clode; Jordan M. Casey; Max C. N. Castorani; Carolina César‐Ávila; Rachel Collin; et al. (Ecology, 2026)
Biogenic structural complexity is a key driver of biodiversity and ecosystem functioning, yet its ecological and environmental determinants remain poorly understood across broad biogeographic scales. Here, we conducted standardized 90‐day field experiments at 16 coastal sites, spanning a 41‐degree latitudinal gradient, using naturally assembled marine fouling communities on settlement panels. We measured rugosity as our metric of biogenic structural complexity and modeled its relationship with species richness, community composition, community growth rates, and abiotic conditions (salinity and temperature). Species richness increased with temperature and salinity and declined with latitude, with more diverse communities exhibiting greater biogenic complexity due to increased morphological variation. At high‐latitude sites, low‐diversity communities dominated by arborescent bryozoans also had increased complexity. Structural equation models showed that abiotic conditions influenced growth and composition, which in turn shaped complexity. Warmer, saltier sites promoted richness‐driven complexity, while colder conditions favored structurally important dominant taxa. We found that biodiversity is important not only as a beneficiary of complexity but also as a contributor to complexity itself within fouling communities. Our results also demonstrate that both species richness and functional group identity regulate biogenic complexity across environmental gradients, underscoring biodiversity's role in supporting ecosystem structure and resilience in the face of increasing global change. Understanding these relationships is essential for biodiversity conservation and the management of marine ecosystems facing increasing anthropogenic pressures.

Integrated Reanalysis of Global Riverine Fish eDNA Datasets Shows Robustness and Congruence of Biodiversity Conclusions - Yan Zhang; Heng Zhang; Hiroshi Akashi; Camille P. Albouy; Kara J. Andres; José Barquín; Jeanine Brantschen; Richard E. Connon; Joseph M. Craine; Deirdre Gleeson; Alejandra Goldenberg‐Vilar; Alexia M. González‐Ferreras; et al. (Molecular Ecology, 2026)
The analysis of environmental DNA (eDNA) has revolutionized biodiversity assessments in aquatic ecosystems, enabling non‐invasive monitoring of fish communities across diverse regions. However, the global comparability of these eDNA datasets remains ambiguous due to heterogeneous sampling protocols and bioinformatic workflows across studies, making it difficult to assess how robust and comparable the biodiversity patterns inferred from these datasets actually are. Here, we conducted a meta‐analysis of 58 riverine fish eDNA metabarcoding studies, covering 1818 sampling sites worldwide, to evaluate the robustness of eDNA‐derived biodiversity patterns. We found that species richness estimates and metrics of community structure derived under a common bioinformatic workflow were overall consistent with those of original analyses, despite the relatively high variability in bioinformatic analyses in the respective original studies. Contrastingly, congruence of species identity varied more extensively across datasets, mostly reflecting different completeness and regional relevance of reference databases. Restricting taxonomic assignment to basin‐specific species pools improved species identification accuracy, while datasets lacking publicly accessible or well‐curated reference data were more prone to mismatches. Year of sampling had a positive effect on taxonomic congruence, such that more recent studies showed increased robustness, also reflecting improved reference database coverage and enhanced species‐level identification over time and overall method congruence in more recent years. Overall, the suitability and potential of eDNA for global biodiversity monitoring is corroborating overall robust biodiversity estimates, irrespective of the bioinformatic approaches. Our study underlines the effectiveness and need for further harmonization of bioinformatic workflows and strengthened region‐specific reference databases for improved taxonomic resolution and comparability across studies.

High-resolution surface and rootzone soil moisture over US cropland: A novel framework assimilating multi-source remote sensing data, machine learning, and the Layered Green and Ampt Infiltration with Redistribution model - Shuohao Cai; Yijia Xu; Zhengwei Yang; Wade T. Crow; Zhou Zhang; Jiali Shang; Jiangui Liu; Peter La Follette; Chris Reberg-Horton; Harry Schomberg; Steven Mirsky; Brian Davis; et al. (Remote Sensing of Environment, 2026)

‘Building the (Im)perfect Beast’: Strategies for Identifying Appropriate Spatial Stock Assessment Model Complexity From an International, Blinded High‐Resolution Simulation Experiment - Aaron M. Berger; Daniel R. Goethel; Simon D. Hoyle; Patrick Lynch; Caren Barceló; Alistar Dunn; Brian J. Langseth; Carolina Minte‐Vera; Jemery Day; Haikun Xu; Francisco Izquierdo; Dan Fu; et al. (Fish and Fisheries, 2026)
Despite their potential to inform sustainable regional harvest and climate‐resilient fisheries management, spatial stock assessment models remain underused for management advice. To identify barriers that inhibit broader use of these methods, we conducted a blinded international simulation experiment mimicking real‐world stock assessment development when confronting spatial complexity. Seven analyst teams built spatially aggregated and spatially explicit assessment models using data simulated from high‐resolution operating models based on Indian Ocean yellowfin tuna and Ross Sea Antarctic toothfish dynamics. Each team documented how assessment software platform, data analyses, model building approach, and diagnostics influenced model complexity and realism. A consensus emerged on key assessment building approaches: (1) conduct high‐resolution data analyses to identify appropriate spatial structure; (2) start with simplified models and incrementally add complexity; (3) iteratively evaluate diagnostics to determine necessary spatial complexity; and (4) maintain models with different spatial structures to aid interpretation. The experiment also revealed several valuable insights for parameterising assessments, including consideration of data pre‐processing with spatiotemporal models to better inform data‐sparse regions; regression trees to identify fleet and spatial structure; trade‐offs in complexity between productivity and movement dynamics to achieve tractable and stable model structures; and ensemble modelling approaches to address structural uncertainty. Our findings demonstrate that international collaborations and simulation experiments are crucial for addressing challenges in implementing spatial stock assessments and for evaluating whether their added complexity is justified given management objectives. Broader collaborations are encouraged to foster innovation in fisheries management and to help recognise the practical trade‐offs between model parsimony and complexity.

Angler Heterogeneity in Newfoundland and Labrador, Canada: Insights From Nearly Three Decades (1994–2022) of Atlantic Salmon Angler License and Activity Records - Travis E. Van Leeuwen; Michelle G. Fitzsimmons; J. Brian Dempson; Christopher W. White; Mark Young; Donald Keefe; Isabelle Schmelzer; Nicholas I. Kelly; Craig F. Purchase; Blair Adams; David Coté (Fisheries Management and Ecology, 2026)
Angler demographics and motivations are an important consideration to successful fisheries management. We examined 29 years of angler license and activity records from the recreational Atlantic salmon fishery in Newfoundland and Labrador, Canada to: (1) provide a contemporary evaluation of angler demographic trends; (2) evaluate age and regional differences between anglers who prioritized retention versus catch‐and‐release; and (3) discuss how various management and COVID restrictions affected angler participation and activity. Resident license holders made up 91.3% of total licenses purchased. The average age of license holders increased from 39 years of age in 1994 to 54 years of age in 2022, with 6–20 year olds making up

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Drone multispectral imaging reveals seasonal microphytobenthos drivers at shorebird foraging sites - Tristan J. Douglas; Nicholas C. Coops; Mark C. Drever; Brian P.V. Hunt; Tara G. Martin; Robert W. Elner (Remote Sensing Applications: Society and Environment, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Multi-trophic interactions and niche partitioning in the native range informs biological control in forests invaded by the hemlock woolly adelgid - Nicholas J. Dietschler; Fangzhou Liu; Sabrina L. Celis; Mark C. Whitmore; Anurag A. Agrawal (Biological Invasions, 2026)
Understanding natural enemy communities in the native range of pest insects is critical for implementing management decisions where such pests are invasive. The hemlock woolly adelgid (HWA) is a destructive invasive insect, causing decline of hemlock forests in eastern North America. We studied patterns of predator coexistence and prey suppression among native predators in western North America to inform biological control strategies in the invaded eastern range. In particular, we examined the structure and interactions of HWA’s specialist predator complex (a beetle Laricobius nigrinus , and two flies Leucotaraxis argenticollis and Le. piniperda ) across five western populations over two years. Field surveys quantified spatial and temporal overlap, while a laboratory experiment assessed competition between the two Leucotaraxis species. We employed species-specific RT-qPCR to quantify populations of cryptic Leucotaraxis immatures. Supporting the notion of complementary predation, predators exhibited clear temporal and spatial niche partitioning: (1) the two Leucotaraxis species were temporally separated, (2) while La. nigrinus overlapped with both Leucotaraxis species, they showed negative spatial co-occurrence on twigs, and (3) no evidence of competition between Leucotaraxis species was observed in the lab. These native predators appear to partition resources facilitating prey suppression, and they may be complementary in biological control. Nonetheless, during our study we observed only one HWA pest generation annually in the native western range, contrasting with bivoltine populations in the invaded east. This difference in pest voltinism, along with climatic differences between native and invaded communities, will likely influence predator–prey synchrony as the natural enemy complex establishes in invaded range.

Characterizing canopy light penetration in black walnut (Juglans nigra) cultivars to inform selection for alley cropping - Benjamin Bishop; Fernando Torralbo; Nicholas A. Meier; Mark Coggeshall; Felix B. Fritschi; Ronald S. Revord (Agroforestry Systems, 2026)
Eastern black walnut ( Juglans nigra L.) is a nut-producing tree species that breaks dormancy late in the spring, allowing a winter alley crop to ripen before substantial canopy shade is formed. However, there is a high level of variation in the timing and structure of tree canopy development within the black walnut cultivar collection maintained at the University of Missouri Center for Agroforestry (UMCA). To identify cultivars with high levels of compatibility with winter alley cropping, we measured the amount of photosynthetically-active radiation transmitted (PARt) through the canopy. Eight physical traits were also measured to assess their relationship with light interception and to gain insight on characters that lead to greater understory light extinction. Significant differences between cultivars were seen in PARt, particularly on Julian date 132 (May 12) where a two-fold difference was observed in PARt between the most contrasting cultivars. Traits such as date of bud break, tree shape and live canopy ratio were associated with levels of PARt, providing preliminary support for strong component drivers of light displacement/penetration during spring. This study provides the first exploration of genetic variation in black walnut for above-ground compatibility with an understory crop, and in doing so, reports meaningful genetic variation exists for study and use. New context is reported for design of subsequent genetic, physiological, and plant-plant interaction studies. For example, there is not a negative relationship between leafing duration and fruit production, and late-leafing varieties, which are more suitable for agroforestry, remain productive in comparison to early-leafing ones. Additionally, these data may inform the selection or breeding of cultivars with improved complementary for alley cropping with winter grains, as well as management strategies (pruning) to improve light penetration in black walnut alley cropping systems.

BMP9 knockout impairs pulmonary vessel muscularisation and confers aberrant tamoxifen sensitivity - Benjamin J. Dunmore; Stephen Moore; Rowena J. Jones; Joshua Hodgson; Kathryn Auckland; Mark Southwood; Nichola Figg; Nobuhiro Kikuchi; Martin Bennett; Allan Lawrie; Christopher J. Rhodes; Mark R. Toshner; et al. (Angiogenesis, 2025)
Deleterious mutations in the GDF2 gene, encoding BMP9, are causative of pulmonary arterial hypertension and hereditary haemorrhagic telangiectasia. Paradoxically, BMP9 germ-line knockout ( Gdf2 −/− ; Bmp9 KO) and double Bmp9 KO / conditional Bmp10 cKO (dKO) mice exhibit an attenuated response to PAH-inducing stimuli. We asked whether this contradiction is due to the pathological, physiological, or genetic consequences of BMP9 knockout. In Bmp9 KO mice we observed reduced pulmonary vascular smooth muscle cell (SMC) coverage and using RNA-seq analysis of Bmp9 KO mouse lungs identified two novel genes, COLQ and ITGA6 , which were differentially regulated in a human PAH RNA-seq dataset. In order to study BMP10 loss, postnatal tamoxifen treatment was required to induce Bmp10 cKO. As previously reported, in dKO mice we observed cardiomegaly and splenomegaly, as well as hyperplasia and hemosiderosis in the pulmonary vasculature. Surprisingly, tamoxifen treated Bmp9 KO control mice phenocopied these pathological changes in dKO mice and downregulated SMC marker gene transcription. Loss of BMP10 is not critical for severe tissue remodelling in the lung, heart, and spleen, rather Bmp9 KO mice appear sensitive to tamoxifen and BMP9 loss is the primary cause of mild vessel remodelling due to a basal reduction of smooth muscle cell coverage. This study suggests that interaction of the BMP pathway with tamoxifen needs to be carefully considered when studying Bmp9 KO mice and urges caution in the context of tamoxifen use when studying cardiovascular and pulmonary disease models.

Methodological considerations for studying spectral-plant diversity relationships - Christine I.B. Wallis; Anna L. Crofts; Robert Jackisch; Shan Kothari; Guillaume Tougas; J. Pablo Arroyo-Mora; Paul Hacker; Nicholas Coops; Margaret Kalacska; Etienne Laliberté; Mark Vellend (Remote Sensing of Environment, 2025)

Observed seasonal trends of diatom-derived C20 highly branched isoprenoids (HBIs): implications for paleoclimate studies - Megan C. Corcoran; Aaron F. Diefendorf; Nicholas Wiesenberg; Thomas V. Lowell; Gregory C. Wiles; Mark A. Wilson; Broxton W. Bird; Hans Naake; Watts L. Dietrich (Geochimica et Cosmochimica Acta, 2025)

Tailored toxins: Coagulotoxic variations in Atropoides, Cerrophidion, Metlapilcoatlus, and Porthidium viperid venoms against diverse vertebrate plasmas - Lee Jones; Edgar Neri-Castro; Nicholas J. Youngman; Joshua Llinas; Mark Haworth; Amber Gillett; Bryan G. Fry (Toxicon, 2025)

Porosity and hydrous alteration of the Martian crust from InSight seismic data - Brigitte Knapmeyer-Endrun; Ludmila Adam; Sebastian Carrasco; Matthew P. Golombek; Doyeon Kim; Martin Knapmeyer; Katarina Miljković; Ana-Catalina Plesa; Nicholas H. Warner; Mark Wieczorek (Physics of the Earth and Planetary Interiors, 2025)

Genotype-by-environment interaction in production traits of yellowtail kingfish (Seriola lalandi) reared in RAS and flow through systems - Nicholas K. Jacob; Mark Camara; Alvin Setiawan; John W.M. Bastiaansen (Aquaculture, 2025)

Utilising on-farm risk assessment data for the management of Johne’s disease in dairy cattle in Northern Ireland - Emma Nicole Taylor-Holt; Sam Strain; Nicholas Mark Taylor; Sitira Williams; Nicholas Wheelhouse; James Hanks; Peter Guy Orpin; David C. Rose; Abel Bulamu Ekiri (Preventive Veterinary Medicine, 2025)

Local inflammation at the salmon louse (Lepeophtheirus salmonis) attachment site contributes to copepodid rejection in coho salmon (Oncorhynchus kisutch) - Lene Sveen; Mark D. Fast; Torstein Tengs; Rachel A. Kline; Judit Aguilar Marti; Dominic Kurian; Gerrit Timmerhaus; Marianne Vaadal; Ross D. Houston; James E. Bron; Sean J. Monaghan; Haitham H. Mohammed; et al. (Cell and Tissue Research, 2025)
The study investigates the susceptibility of Atlantic salmon ( Salmo salar ) and Pacific salmon species (pink salmon, Oncorhynchus gorbuscha ; coho salmon, Oncorhynchus kisutch ; and chum salmon, Oncorhynchus keta ) to the parasitic salmon lice ( Lepeophtheirus salmonis ). The research had two main objectives: to characterize the morphology of the scaly skin in four salmonid species and to compare the cellular response at the louse attachment site in coho salmon and Atlantic salmon. Three consecutive challenge trials were conducted, with successful louse infestation only achieved across all four species in the third trial using mild anesthesia with tricaine methanesulfonate. Skin and fin samples were collected at 12, 24, 36, 48, 60, and 168 h post-infestation (hpi) for histological, proteomic, and spatial transcriptomic analyses. Results showed that chum salmon had significantly higher mucous cell coverage (30–40%) in the epithelium of scaly skin compared to Atlantic salmon (10%). At the louse attachment site in coho salmon, there was a greater influx of inflammatory cells at 36–48 hpi compared to Atlantic salmon. Proteomic analysis at 12 hpi and 36 hpi in coho salmon showed upregulation of neutrophil degranulation and formyl-methionyl-leucyl-phenylalanine signaling. Additionally, spatial transcriptomics at the attachment site showed local upregulation of inflammatory gene markers. These findings suggest that coho salmon mount a rapid and large-scale inflammatory response driven by neutrophils to louse attachment within the first 48 hpi. Overall, the study emphasizes the significance of local changes at the host-parasite interface for resistance mechanisms against salmon lice.

Genomic infrastructure for cetacean research and conservation: reference genomes for eight families spanning the cetacean tree of life - Phillip A. Morin; Bernhard Bein; Chiara Bortoluzzi; Yury V. Bukhman; Taylor Hains; Dorothea Heimeier; Marcela Uliano-Silva; Dominic E. Absolon; Linelle Abueg; Jessica Antosiewicz-Bourget; Jennifer R. Balacco; Robert K. Bonde; et al. (Frontiers in Marine Science, 2025)
Reference genomes from representative species across families provide the critical infrastructure for research and conservation. The Cetacean Genomes Project (CGP) began in early 2020 to facilitate the generation of near error-free, chromosome-resolved reference genomes for all cetacean species. Towards that goal, and using the methods, goals and genome assembly quality standards of the Vertebrate Genomes Project (VGP), we generated 13 new reference genomes across eight of the 14 cetacean families. Additionally, we summarize the genome assembly characteristics for 18 species, including these newly-generated and five published genome assemblies that meet the completeness and quality standards. We infer ancestral linkage groups (ALG) for cetaceans, showing that the ancestral karyotype of 22 ALGs is largely conserved in extant species, except for Ziphiidae, and for Balaenidae and Kogiidae, which exhibit similar independent fusions. Gene annotation, characterization of historical demography, heterozygosity and runs of homozygosity (ROH) reveal important information for conservation applications. By comparing the new reference genomes to previous draft assemblies, we show that the reference genomes have enhanced characteristics that will support and promote scientific research. Specifically, the genomes improve resolution and characterization of repetitive elements, provide validation (or exclusion) of genes linked to complex traits, and allow more complete characterization of gene regions such as the highly complex Major Histocompatibility Complex (MHC) Class I and II gene clusters that are important for population health.

Energetic benefits of prey choice for a shark-eating shark - Erin T. Spencer; Lisa A. Hoopes; Jack J. Morris; Demian D. Chapman; Valerie Hagan; Mark Johnson; Nicholas L. Payne; Yuuki Y. Watanabe; Ruth E. Dunn; Yannis P. Papastamatiou (Oecologia, 2025)

Pharmacokinetics and Pharmacodynamics of Nomlabofusp in Non-clinical Studies of Friedreich’s Ataxia - Flavia De Toni; Vanessa Ragaglia; Devin Schecter; Angela S. Miller; Eric Gonzalez; Erik J. Wagner; Xin Xu; R. Mark Payne; Jean-Nicholas Mess; Matthew G. Baile; Adrienne Clements-Egan; Gopi Shankar (The AAPS Journal, 2025)
Nomlabofusp is a cell penetrant peptide-based recombinant fusion protein designed to enter cells and deliver human frataxin into the mitochondria of adults and children with Friedreich’s ataxia. In this article we present non-clinical studies evaluating the pharmacology of nomlabofusp, including in a murine striated muscle tissue frataxin knockout model of Friedreich’s ataxia. We demonstrate that subcutaneous administration of nomlabofusp distributes in a dose-dependent manner to several organs including the dorsal root ganglion, heart, and skeletal muscle, which are known to be predominantly affected in Friedreich’s ataxia, as well as to other tissues, including skin. Plasma nomlabofusp concentrations correlated with levels of human frataxin delivered by nomlabofusp into tissues, and the increases in frataxin were correlated amongst tissues, especially with skin. In the knockout mice, we show that the pharmacokinetics and processing of nomlabofusp were comparable with wild type animals and that treatment with nomlabofusp halts the progression of cardiac dysfunction and significantly increased survival. Together, the findings from these non-clinical studies demonstrate that nomlabofusp exposure increases human frataxin in Friedreich’s ataxia-relevant tissues and provide evidence of pharmacologic effects. Graphical Abstract

Mechanical site preparation and use of non-invasive cover crops influences early-successional forest vegetation composition of a reclaimed airstrip in the Boreal Forest - Nicholas Harper; Amanda L. Schoonmaker; Andrés G. Rolhauser; Mark Baah-Acheamfour; Ann Smreciu; Erin C. Fraser-Reid (Forest Ecology and Management, 2025)

Reporting Compliance and Factors Influencing Timeliness of Stroke-Related Trial Results on ClinicalTrials.gov - Mark Cwajna; Abdelrahman M. Hamouda; Nicholas Kendall; Sherief Ghozy; Benjamin D. Elder; David F. Kallmes (Translational Stroke Research, 2025)

Understanding predator-prey-competitor dynamics between Lower Missouri River Macrhybopsis and Scaphirhynchus using a population—bioenergetics model ensemble - Mark L. Wildhaber; Janice L. Albers; Nicholas S. Green (Ecological Modelling, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Discrete fracture network model benchmarks developed and applied in a DECOVALEX-2023 repository performance assessment study - Paul E. Mariner; Rosie C. Leone; Emily R. Stein; Jeffrey D. Hyman; Jan Thiedau; Zhenze Li; Son Nguyen; Yong-Min Kim; Jung-Woo Kim; Chieh-Chun Chang; Scott A. Briggs; Mark Gobien; et al. (Geomechanics for Energy and the Environment, 2025)

Predictive alternating runs and random task-switching sequences produce dissociative switch costs in the Consonant–Vowel/Odd–Even task - Nicholas P. Maxwell; Mark J. Huff; Jacob M. Namias (Cognitive Processing, 2025)

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Fatal systemic bacterial infections in two harbour porpoises (Phocoena phocoena) secondary to bite wounds from grey seals (Halichoerus grypus) - Nicholas J. Davison; Mark P. Dagleish; Geoffrey Foster; Anne Ridley; Mariel ten Doeschate; Andrew Brownlow (Journal of Comparative Pathology, 2025)

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Co‐mast: Harmonized seed production data for woody plants across US long‐term research sites - Katherine M. Nigro; Jessica H. Barton; Diana Macias; V. Bala Chaudhary; Ian S. Pearse; David M. Bell; Angel Chen; Natalie L. Cleavitt; Elizabeth E. Crone; David F. Greene; E. Penelope Holland; Jill F. Johnstone; et al. (Ecology, 2025)
Plants display a range of temporal patterns of inter‐annual reproduction, from relatively constant seed production to “mast seeding,” the synchronized and highly variable interannual seed production of plants within a population. Previous efforts have compiled global records of seed production in long‐lived plants to gain insight into seed production, forest and animal population dynamics, and the effects of global change on masting. Existing datasets focus on seed production dynamics at the population scale but are limited in their ability to examine community‐level mast seeding dynamics across different plant species at the continental scale. We harmonized decades of plant reproduction data for 141 woody plant species across nine Long‐Term Ecological Research (LTER) or long‐term ecological monitoring sites from a wide range of habitats across the United States. Plant reproduction data are reported annually between 1957 and 2021 and based on either seed traps or seed and/or cone counts on individual trees. A wide range of woody plant species including trees, shrubs, and lianas are represented within sites allowing for direct community‐level comparisons among species. We share code for filtering of data that enables the comparison of plot and individual tree data across sites. For each species, we compiled relevant life history attributes (e.g., seed mass, dispersal syndrome, seed longevity, sexual system) that may serve as important predictors of mast seeding in future analyses. To aid in phylogenetically informed analyses, we also share a phylogeny and phylogenetic distance matrix for all species in the dataset. These data can be used to investigate continent‐scale ecological properties of seed production, including individual and population variability, synchrony within and across species, and how these properties of seed production vary in relation to plant species traits and environmental conditions. In addition, these data can be used to assess how annual variability in seed production is associated with climate conditions and how that varies across populations, species, and regions. The dataset is released under a CC0 1.0 Universal public domain license.

Community-level responses and environmental fate of metformin in freshwater mesocosms - Nicholas C. Blandford; Vince Palace; José Luis Rodríguez-Gil; Lauren Timlick; Madeline Stanley; Richard A. Frank; Sheena Campbell; Martina Rudy; Stephanie Marshall; Abby Wynia; Thomas Clark; Jessie Cunningham; et al. (Science of The Total Environment, 2024)

Mechanics of the artillery fungus - Nicholas P. Money; Jessica Stolze; Mark W.F. Fischer (Fungal Biology, 2024)

Dynamic rates of Freshwater Drum near the northern extent of their range: evidence of environment-recruitment relationships - Marshall Stuart; Nicholas Kludt; Mark A. Pegg; Federica Montesanto; Cade Lyon; Connor J. Chance-Ossowski (Environmental Biology of Fishes, 2024)

Community Synchrony in Seed Production is Associated With Trait Similarity and Climate Across North America - Jalene M. LaMontagne; David F. Greene; E. Penelope Holland; Jill F. Johnstone; Mark Schulze; Jess K. Zimmerman; Nicholas J. Lyon; Angel Chen; Tom E. X. Miller; Katherine M. Nigro; Rebecca S. Snell; Jessica H. Barton; et al. (Ecology Letters, 2024)
Mast seeding, the synchronous and highly variable production of seed crops by perennial plants, is a population‐level phenomenon and has cascading effects in ecosystems. Mast seeding studies are typically conducted at the population/species level. Much less is known about synchrony in mast seeding between species because the necessary long‐term data are rarely available. To investigate synchrony between species within communities, we used long‐term data from seven forest communities in the U.S. Long‐Term Ecological Research (LTER) network, ranging from tropical rainforest to boreal forest. We focus on cross‐species synchrony and (i) quantify synchrony in reproduction overall and within LTER sites, (ii) test for relationships between synchrony with trait and phylogenetic similarity and (iii) investigate how climate conditions at sites are related to levels of synchrony. Overall, reproductive synchrony between woody plant species was greater than expected by chance, but spanned a wide range of values between species. Based on 11 functional and reproductive traits for 103 species (plus phylogenetic relatedness), cross‐species synchrony in reproduction was driven primarily by trait similarity with phylogeny being largely unimportant, and synchrony was higher in sites with greater climatic water deficit. Community‐level synchrony in masting has consequences for understanding forest regeneration dynamics and consumer‐resource interactions.

The use of conceptual models to structure stock assessments: A tool for collaboration and for “modelling what to model” - Carolina V. Minte-Vera; Mark N. Maunder; Alexandre Aires-da-Silva; Haikun Xu; Juan L. Valero; Steven L.H. Teo; Patrício Barría; Nicholas D. Ducharme-Barth (Fisheries Research, 2024)

Changes in the Johne’s disease situation in GB dairy herds over 10 years, as revealed by regular milk ELISA data - Emma Nicole Taylor; Kulwant Channa; Pete Guy Orpin; James Hanks; Nicholas Mark Taylor (Preventive Veterinary Medicine, 2024)

Recent and sustainable advances in phytoremediation of heavy metals from wastewater using aquatic plant species: Green approach - Jonas Bayuo; Mwemezi J. Rwiza; Joon Weon Choi; Karoli Nicholas Njau; Kelvin Mark Mtei (Journal of Environmental Management, 2024)

Environmental conditions outweigh seeding rates for cover crop mixture performance across the Northeast US - Helen S. Boniface; Steven B. Mirsky; Matthew R. Ryan; Richard G. Smith; Victoria J. Ackroyd; K. Ann Bybee-Finley; Heather M. Darby; Sjoerd W. Duiker; Masoud Hashemi; Sarah M. Hirsh; Ivy Krezinski; Ellen B. Mallory; et al. (Field Crops Research, 2024)

Toward a comprehensive phylogeny of North American bladderworts (Utricularia, Lentibulariaceae) - Nicholas P. Tippery; James Moreland; Theodore Wild; Gregory J. Bugbee; Summer E. Stebbins; James G. Mickley; Alan R. Franck; Keir M. Wefferling; Mark J. Warman (Aquatic Botany, 2024)

Synthesis and Pharmacological Characterization of Adrenocorticotropic Hormone (ACTH 1–24) and C-Terminal Truncated Analogues Identifies the Minimal ACTH N-Terminal Fragment Required for Melanocorton-2 Receptor Activation - Aleksandar Todorovic; Mark D. Ericson; Kelly Gridley; Nicholas B. Sorenson; Carrie Haskell-Luevano (International Journal of Peptide Research and Therapeutics, 2024)

Threat assessment for Pacific sand lance (Ammodytes personatus) in the Salish Sea - Jacqueline R. Huard; Victoria Hemming; Matthew R. Baker; Jennifer Blancard; Ian Bruce; Sarah Cook; Gail K. Davoren; Phillip Dionne; Virginia East; J. Mark Hipfner; Nicola R. Houtman; Brian A. Koval; et al. (Frontiers in Marine Science, 2024)
Like many forage fish species, Pacific sand lance ( Ammodytes personatus ) play a key role in nearshore marine ecosystems as an important prey source for a diverse array of predators in the northeastern Pacific. However, the primary threats to Pacific sand lance and their habitat are poorly defined due to a lack of systematic data. Crucial information needed to assess their population status is also lacking including basic knowledge of their local and regional abundance and distribution. Sand lance are currently listed as ‘not evaluated’ under the IUCN red list and they have not been assessed by US and Canadian agencies. This hampers management and policy efforts focused on their conservation. To address this knowledge gap, we conducted a three-part, structured expert elicitation to assess the vulnerability of Salish Sea sand lance populations. Experts were asked to list and rank key threats to Salish Sea sand lance and/or their habitat, to further quantify the vulnerability of sand lance to identified threats using a vulnerability matrix, and to predict the population trajectory in 25 years from today. Impacts associated with climate change (e.g. sea level rise, sea temperature rise, ocean acidification, and extreme weather) consistently ranked high as threats of concern in the ranking exercise and quantified vulnerability scores. Nearly every expert predicted the population will have declined from current levels in 25 years. These results suggest sand lance face numerous threats and may be in decline under current conditions. This research provides vital information about which threats pose the greatest risk to the long-term health of sand lance populations and their habitat. Managers can use this information to prioritize which threats to address. Future research to reliably quantify population size, better understand the roles of natural and anthropogenic impacts, and to identify the most cost-effective actions to mitigate multiple threats, is recommended.

Quantitative trait loci for bearing habit in a ‘Sparrow’ × ‘Schessler’ Juglans nigra mapping population - Benjamin Jablonski; Nicholas A. Meier; Warren Chatwin; Mark V. Coggeshall; Jeanne Romero-Severson; Ronald S. Revord (Tree Genetics & Genomes, 2024)
Eastern black walnut, Juglans nigra L., is an economically important tree species valued for its high-quality timber and edible nuts. A regional industry for the species’ nut and kernel products resides in Missouri, where over 9 million kg of hulled in-shell nuts are purchased in masting years. The crop is primarily based upon nuts harvested from wild trees, placing a ceiling on nut volume and quality (e.g. small nut size, dark pellicle color, and 10–14% kernel by weight). Orchards of named cultivars, like ‘Kwik Krop’ and ‘Sparrow’, supply up to 22,000 kg of nuts with a higher kernel percentage (> 26%) and improved quality. Such cultivars often represent chance wild or on-farm seedlings, clonally propagated since the late 1800’s by enthusiasts. Today, continued improvement of eastern black walnut as an orchard crop is limited by a long generation time, delayed expression of important traits, and space requirements – creating a strong need for marker-trait association studies that inform progeny selection. The first linkage map for J. nigra was recently created using the ‘Sparrow’ × ‘Schessler’ F 1 population and loci for phenology traits discovered. The objective of this study is to utilize these genetic resources to detect quantitative trait loci (QTL) and report associated DNA markers for the spur-bearing habit, which promotes precocity and high yield. Using single-year data from the 11-year-old population, we observe that segregation for the spur-bearing habit appears to be recessive and multigenic. Three QTLs (p > 0.99) were identified on linkage group (LG) 8, LG11, and LG16 that explain 7.2%, 8.7%, and 10% of trait variation, respectively. Regions between flanking DNA markers were 3.16 cM, 4.32 cM, and 9.69 cM, respectively. This study is the first to examine the genetic control of bearing habit and yield in eastern black walnut and informs breeders’ approach for their future genetic improvement.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Linking microphytobenthos distribution and mudflat geomorphology under varying sedimentary regimes using unoccupied aerial vehicle (UAV)-acquired multispectral reflectance and photogrammetry - Tristan J. Douglas; Nicholas C. Coops; Mark C. Drever; Brian P.V. Hunt; Tara G. Martin (Science of The Total Environment, 2024)

Stable isotope evidence for resource partitioning in extinct marine carnivores - Ana M. Valenzuela-Toro; Nicholas D. Pyenson; Daniel P. Costa; Mark Clementz; Paul L. Koch (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Stable isotopes and diet metabarcoding reveal trophic overlap between native and invasive Banded Killifish (Fundulus diaphanus) subspecies - Jordan H. Hartman; Mark A. Davis; Nicholas J. Iacaruso; Jeremy S. Tiemann; Eric R. Larson (Environmental Biology of Fishes, 2024)

The distribution of global tidal marshes from Earth observation data - Thomas A. Worthington; Mark Spalding; Emily Landis; Tania L. Maxwell; Alejandro Navarro; Lindsey S. Smart; Nicholas J. Murray (Global Ecology and Biogeography, 2024)
Aim Tidal marsh ecosystems are heavily impacted by human activities, highlighting a pressing need to address gaps in our knowledge of their distribution. To better understand the global distribution and changes in tidal marsh extent, and identify opportunities for their conservation and restoration, it is critical to develop a spatial knowledge base of their global occurrence. Here, we develop a globally consistent tidal marsh distribution map for the year 2020 at 10‐m resolution. Location Global. Time period 2020. Major taxa studied Tidal marshes. Methods To map the location of the world's tidal marshes at 10‐m resolution, we applied a random forest classification model to Earth observation data from the year 2020. We trained the classification model with a reference dataset developed to support distribution mapping of coastal ecosystems, and predicted the spatial distribution of tidal marshes between 60° N and 60° S. We validated the tidal marsh map using standard accuracy assessment methods, with our final map having an overall accuracy score of 0.85. Results We estimate the global extent of tidal marshes in 2020 to be 52,880 km 2 (95% CI: 32,030 to 59,780 km 2 ) distributed across 120 countries and territories. Tidal marsh distribution is centred in temperate and Arctic regions, with nearly half of the global extent of tidal marshes occurring in the temperate Northern Atlantic (45%) region. At the national scale, over a third of the global extent (18,510 km 2 ; CI: 11,200–20,900) occurs within the USA. Main conclusions Our analysis provides the most detailed spatial data on global tidal marsh distribution to date and shows that tidal marshes occur in more countries and across a greater proportion of the world's coastline than previous mapping studies. Our map fills a major knowledge gap regarding the distribution of the world's coastal ecosystems and provides the baseline needed for measuring changes in tidal marsh extent and estimating their value in terms of ecosystem services.

Stormwise: Innovative Forest Management to Promote Storm Resistance in Roadside Forests - Thomas Worthley; Amanda Bunce; Anita T Morzillo; Chandi Witharana; Zhe Zhu; Jacob Cabral; Emlyn Crocker; Nicholas Cranmer; Steven DiFalco; Daniel Hale; Durga Joshi; Danielle P Kloster; et al. (Journal of Forestry, 2024)
A growing proportion of forested landscapes are interspersed with human infrastructure, such as utility lines and roads, increasing the potential for tree-failure consequences due to storms and other causes. Utilities and other institutions have strong incentives to reduce such interactions and allocate substantial resources to risk reduction, but trees and forests in densely populated landscapes also provide significant amenities to society. We present a generalized framework for “Stormwise” forest management, focused on resistance of roadside forests to storms, based on elements of arboricultural and silvicultural practice and tree biomechanics and architecture. We detail results of a multidisciplinary research program focused on management outcomes, opportunities and barriers to implementation, and allocation of investment based on physical and social landscape characteristics. We discuss initial findings, the potential for widespread adoption of resilience-focused management in roadside and infrastructure-adjacent forests, and the importance of such work, considering a changing climate. Study Implications: The research and implementation program we detail here illustrates the potential for “Stormwise” forest management to reduce storm-damage recovery costs, result in fewer and shorter-duration power and transportation interruptions, and allow for low-investment ground-based management in future forest entries. We illustrate a multifaceted, interdisciplinary research program that links the geospatial, social, and biophysical components of understanding forest infrastructure systems. We illustrate how implementation of Stormwise management has the potential to benefit stakeholders such as residents and utilities, offset the substantial economic costs of tree-related power outages, and reduce societal disruptions associated with interactions between trees and infrastructure during storms.

Should I stay or should I go? The influence of environmental conditions on green turtle residence time and outward transit in foraging areas - Emily G. Webster; Stephanie Duce; Mark Hamann; Nicholas Murray; Takahiro Shimada; Colin Limpus (Marine Biology, 2024)
Foraging animals move through the environment to satisfy their requirements for food, rest, reproduction and risk-avoidance. Understanding how animals respond to changing environmental conditions can help to characterise favourable habitat and determine whether they might be motivated to depart when those habitats become unsuitable. Foraging green turtles are typically residents that scarcely move in response to environmental changes or disturbances. Some individuals though, exhibit high mobility at fine scales. We developed an analysis of Fastloc GPS tracks of 61 green turtles using cox regression models and generalised linear mixed models to investigate the influence of a suite of environmental characteristics on the length of residence time and probability of turtles transitioning between two behavioural modes, “stay” or “go”. Decisions to move (“go”) were influenced by short-term changes in the local environmental conditions. Individuals were more likely to “stay” when temperature increased during their stay and were more likely to “go” when turbidity decreased, and they entered deeper habitats. This result implies that foraging and resting (“staying”) primarily occurs in benthic, shallow, warm habitats, while transit (“going”) is facilitated in deeper, clear water. We also determined that individuals within the green turtle foraging aggregation respond differently to environmental cues to move and hypothesise that a diversity of strategies within a foraging aggregation could confer its resilience to disturbance events. Our study provides new evidence of the factors influencing movements in green turtles and can aid in predicting how they may respond to future changes and enhance risk mitigation efforts through dynamic and adaptive planning.

Effects of metformin on wild fathead minnows (Pimephales promelas) using in-lake mesocosms in a boreal lake ecosystem - Erin Ussery; Mark McMaster; Vince Palace; Joanne Parrott; Nicholas C. Blandford; Richard Frank; Karen Kidd; Oana Birceanu; Joanna Wilson; Mehran Alaee; Jessie Cunningham; Abby Wynia; et al. (Science of The Total Environment, 2024)

Investigation into the stability of synthetic goethite after dynamic shock compression - Nicholas R. Jenkins; Xuan Zhou; Mithun Bhowmick; Claire L. McLeod; Mark P. S. Krekeler (Physics and Chemistry of Minerals, 2024)

Tracking data highlight the importance of human-induced mortality for large migratory birds at a flyway scale - Juan Serratosa; Steffen Oppel; Shay Rotics; Andrea Santangeli; Stuart H.M. Butchart; Luis S. Cano-Alonso; Jose Luis Tellería; Ryno Kemp; Aaron Nicholas; Aigars Kalvāns; Aitor Galarza; Aldina M.A. Franco; et al. (Biological Conservation, 2024)

‘Drivin' with your eyes closed’: Results from an international, blinded simulation experiment to evaluate spatial stock assessments - Daniel R. Goethel; Aaron M. Berger; Simon D. Hoyle; Patrick D. Lynch; Caren Barceló; Jonathan Deroba; Nicholas D. Ducharme‐Barth; Alistair Dunn; Dan Fu; Francisco Izquierdo; Craig Marsh; Haikun Xu; et al. (Fish and Fisheries, 2024)
Spatial models enable understanding potential redistribution of marine resources associated with ecosystem drivers and climate change. Stock assessment platforms can incorporate spatial processes, but have not been widely implemented or simulation tested. To address this research gap, an international simulation experiment was organized. The study design was blinded to replicate uncertainty similar to a real‐world stock assessment process, and a data‐conditioned, high‐resolution operating model (OM) was used to emulate the spatial dynamics and data for Indian Ocean yellowfin tuna ( Thunnus albacares ). Six analyst groups developed both single‐region and spatial stock assessment models using an assessment platform of their choice, and then applied each model to the simulated data. Results indicated that across all spatial structures and platforms, assessments were able to adequately recreate the population trends from the OM. Additionally, spatial models were able to estimate regional population trends that generally reflected the true dynamics from the OM, particularly for the regions with higher biomass and fishing pressure. However, a consistent population biomass scaling pattern emerged, where spatial models estimated higher population scale than single‐region models within a given assessment platform. Balancing parsimony and complexity trade‐offs were difficult, but adequate complexity in spatial parametrizations (e.g., allowing time‐ and age‐variation in movement and appropriate tag mixing periods) was critical to model performance. We recommend expanded use of high‐resolution OMs and blinded studies, given their ability to portray realistic performance of assessment models. Moreover, increased support for international simulation experiments is warranted to facilitate dissemination of methodology across organizations.

Does urbanisation lead to parallel demographic shifts across the world in a cosmopolitan plant? - Aude E. Caizergues; James S. Santangelo; Rob W. Ness; Fabio Angeoletto; Daniel N. Anstett; Julia Anstett; Fernanda Baena‐Diaz; Elizabeth J. Carlen; Jaime A. Chaves; Mattheau S. Comerford; Karen Dyson; Mohsen Falahati‐Anbaran; et al. (Molecular Ecology, 2024)
Urbanisation is occurring globally, leading to dramatic environmental changes that are altering the ecology and evolution of species. In particular, the expansion of human infrastructure and the loss and fragmentation of natural habitats in cities is predicted to increase genetic drift and reduce gene flow by reducing the size and connectivity of populations. Alternatively, the ‘urban facilitation model’ suggests that some species will have greater gene flow into and within cities leading to higher diversity and lower differentiation in urban populations. These alternative hypotheses have not been contrasted across multiple cities. Here, we used the genomic data from the GLobal Urban Evolution project (GLUE), to study the effects of urbanisation on non‐adaptive evolutionary processes of white clover ( Trifolium repens ) at a global scale. We found that white clover populations presented high genetic diversity and no evidence of reduced N e linked to urbanisation. On the contrary, we found that urban populations were less likely to experience a recent decrease in effective population size than rural ones. In addition, we found little genetic structure among populations both globally and between urban and rural populations, which showed extensive gene flow between habitats. Interestingly, white clover displayed overall higher gene flow within urban areas than within rural habitats. Our study provides the largest comprehensive test of the demographic effects of urbanisation. Our results contrast with the common perception that heavily altered and fragmented urban environments will reduce the effective population size and genetic diversity of populations and contribute to their isolation.

Apportioning the molybdenum budget in shales to improve paleoenvironmental interpretations - Haolin Zhou; Mark A. Torres; Nicholas B. Harris; Gelu Costin; Tanguy Terlier (Geochimica et Cosmochimica Acta, 2024)

What waterfowl hunters want: exploring heterogeneity in hunting trip preferences - Katherine A. Sainsbury; Howard W. Harshaw; David C. Fulton; Nicholas W. Cole; Ashley A. Dayer; Jennie N. Duberstein; Andrew H. Raedeke; Rudy M. Schuster; Mark P. Vrtiska (Wetlands, 2024)
Canadian and American waterfowl hunters were surveyed to identify their hunting trip preferences. Respondents were individuals that were now participating or had participated in waterfowl hunting, and most had hunted the majority of the last five years. We identified four latent classes of waterfowl hunters that varied in their preferences for harvest, access effort, length of travel, quantity of waterfowl seen, and the potential for interference/competition. We found a diminishing return associated with the number of waterfowl harvested, and that ‘devoted’ and ‘local’ hunters did not perceive appreciable benefit from harvesting more birds beyond harvesting a single bird. Results highlight the importance of not only considering population size, but also the location of habitat for people and waterfowl. Our results provide waterfowl managers important insights into the heterogeneity of North American waterfowl hunters by highlighting differences in priorities for waterfowl hunting trips. Notably, to address this heterogeneity, managers could consider the balance of objectives, actions and resources designed to satisfy current waterfowl hunters. Managing access to improve the likelihood that hunters will see and have opportunities to harvest some waterfowl has benefit to hunters.

Host avian species and environmental conditions influence the microbial ecology of brood parasitic brown‐headed cowbird nestlings: What rules the roost? - Elizabeth N. Rudzki; Nicholas D. Antonson; Todd M. Jones; Wendy M. Schelsky; Brian K. Trevelline; Mark E. Hauber; Kevin D. Kohl (Molecular Ecology, 2024)
The role of species interactions, as well as genetic and environmental factors, all likely contribute to the composition and structure of the gut microbiome; however, disentangling these independent factors under field conditions represents a challenge for a functional understanding of gut microbial ecology. Avian brood parasites provide unique opportunities to investigate these questions, as brood parasitism results in parasite and host nestlings being raised in the same nest, by the same parents. Here we utilized obligate brood parasite brown‐headed cowbird nestlings (BHCO; Molothrus ater ) raised by several different host passerine species to better understand, via 16S rRNA sequencing, the microbial ecology of brood parasitism. First, we compared faecal microbial communities of prothonotary warbler nestlings (PROW; Protonotaria citrea ) that were either parasitized or non‐parasitized by BHCO and communities among BHCO nestlings from PROW nests. We found that parasitism by BHCO significantly altered both the community membership and community structure of the PROW nestling microbiota, perhaps due to the stressful nest environment generated by brood parasitism. In a second dataset, we compared faecal microbiotas from BHCO nestlings raised by six different host passerine species. Here, we found that the microbiota of BHCO nestlings was significantly influenced by the parental host species and the presence of an inter‐specific nestmate. Thus, early rearing environment is important in determining the microbiota of brood parasite nestlings and their companion nestlings. Future work may aim to understand the functional effects of this microbiota variability on nestling performance and fitness.

A new framework for evaluating dust emission model development using dichotomous satellite observations of dust emission - Mark Hennen; Adrian Chappell; Nicholas P. Webb; Kerstin Schepanski; Matthew C. Baddock; Frank D. Eckardt; Tarek Kandakji; Jeffrey A. Lee; Mohamad Nobakht; Johanna von Holdt (Science of The Total Environment, 2024)

Spatial distribution of selenium-mercury in Arctic seabirds - Marta Cruz-Flores; Jérémy Lemaire; Maud Brault-Favrou; Signe Christensen-Dalsgaard; Carine Churlaud; Sébastien Descamps; Kyle Elliott; Kjell Einar Erikstad; Alexey Ezhov; Maria Gavrilo; David Grémillet; Gaël Guillou; et al. (Environmental Pollution, 2024)

Sicklefin Chub (Macrhybopsis meeki) and Sturgeon Chub (M. gelida) Temporal and Spatial Patterns from Extant Population Monitoring and Habitat Data Spanning 23 Years - Mark L. Wildhaber; Benjamin M. West; Kendell R. Bennett; Jack H. May; Janice L. Albers; Nicholas S. Green (Fishes, 2024)
Sicklefin (Macrhybopsis meeki) and sturgeon chub (M. gelida) historically occurred throughout the Missouri River (MR), in some tributaries, and Mississippi River downstream of the MR. They have been species of U.S. state-level conservation concern and U.S. Endangered Species Act listing candidates since the 1990s. We applied analytical approaches from occupancy modeling to correlation to monitoring data spanning 23 years to assess relationships between occupancy and time, space, environmental factors, habitat, and other species. Sicklefin chub occupancy appeared higher in the early to mid-2000s and mid-to-late 2010s. A potential decline in occupancy occurred for sturgeon chub in the mid-to-late 2010s. Spatially, chub occupancy was depressed for 159 to 438 km downstream of MR dams. Among macrohabitats, inside bends had relatively high occupancy for both species; secondary connected channels had relatively high values for sturgeon chub. Co-occurrence was likely between sicklefin and sturgeon chub and between chubs and shovelnose sturgeon (Scaphirhybchus platorybchus) and channel catfish (Ictalurus punctatus). The observed co-occurrence of chubs and pallid sturgeon (Scaphirhynchus albus; PS) was potentially higher than expected for adult PS. For juvenile PS, co-occurrence was lower than expected in the Lower MR and potentially higher than expected in the Upper MR, warranting future research. Results from this research suggest management for the improvement of sicklefin and sturgeon chub populations may benefit other MR fish populations.

Catch per unit effort modelling for stock assessment: A summary of good practices - Simon D. Hoyle; Robert A. Campbell; Nicholas D. Ducharme-Barth; Arnaud Grüss; Bradley R. Moore; James T. Thorson; Laura Tremblay-Boyer; Henning Winker; Shijie Zhou; Mark N. Maunder (Fisheries Research, 2024)

The first report of Listeria monocytogenes detected in pinnipeds - Johanna L. Baily; Gavin K. Paterson; Geoffrey Foster; Nicholas J. Davison; Lineke Begeman; Ailsa J. Hall; Mark P. Dagleish (Journal of Comparative Pathology, 2024)

Utilisation of molecularly imprinting technology for the detection of glucocorticoids for a point of care surface plasmon resonance (SPR) device - Chester Blackburn; Mark V. Sullivan; Molly I. Wild; Abbie J. O’ Connor; Nicholas W. Turner (Analytica Chimica Acta, 2024)

De novo genome and transcriptome assembly of Kelletia kelletii, a coastal gastropod and fisheries species exhibiting a northern range expansion - Benjamin N. Daniels; Cassidy L. Andrasz; Nicholas Zarate; Andy Lee; Cataixa López; Paul Anderson; Robert J. Toonen; Mark R. Christie; Crow White; Jean M. Davidson (Frontiers in Marine Science, 2023)
Understanding the genomic characteristics of non-model organisms can bridge research gaps between ecology and evolution. However, the lack of a reference genome and transcriptome for these species makes their study challenging. Here, we complete the first full genome and transcriptome sequence assembly of the non-model organism Kellet’s whelk, Kelletia kelletii , a marine gastropod exhibiting a poleward range expansion coincident with climate change. We used a combination of Oxford Nanopore Technologies, PacBio, and Illumina sequencing platforms and integrated a set of bioinformatic pipelines to create the most complete and contiguous genome documented among the Buccinoidea superfamily to date. Genome validation revealed relatively high completeness with low missing metazoan Benchmarking Universal Single-Copy Orthologs (BUSCO) and an average coverage of ∼70x for all contigs. Genome annotation identified a large number of protein-coding genes similar to some other closely related species, suggesting the presence of a complex genome structure. Transcriptome assembly and analysis of individuals during their period of peak embryonic development revealed highly expressed genes associated with specific Gene Ontology (GO) terms and metabolic pathways, most notably lipid, carbohydrate, glycan, and phospholipid metabolism. We also identified numerous heat shock proteins (HSPs) in the transcriptome and genome that may be related to coping with thermal stress during the sessile life history stage. A robust reference genome and transcriptome for the non-model organism K. kelletii provide resources to enhance our understanding of its ecology and evolution and potential mechanisms of range expansion for marine species facing environmental changes.

Ascus function: From squirt guns to ooze tubes - Nicholas P. Money; Jessica Stolze-Rybczynski; B. Eugene Smith; Dragana Trninić; Diana J. Davis; Mark W.F. Fischer (Fungal Biology, 2023)

Ancient DNA is preserved in fish fossils from tropical lake sediments - Moritz Muschick; Eliane Jemmi; Nicholas Lengacher; Stephanie Hänsch; Nathan Wales; Mary A. Kishe; Salome Mwaiko; Jorunn Dieleman; Mark Alexander Lever; Walter Salzburger; Dirk Verschuren; Ole Seehausen (Molecular Ecology, 2023)
Tropical freshwater lakes are well known for their high biodiversity, and particularly the East African Great Lakes are renowned for their adaptive radiation of cichlid fishes. While comparative phylogenetic analyses of extant species flocks have revealed patterns and processes of their diversification, little is known about evolutionary trajectories within lineages, the impacts of environmental drivers, or the scope and nature of now‐extinct diversity. Time‐structured palaeodata from geologically young fossil records, such as fossil counts and particularly ancient DNA (aDNA) data, would help fill this large knowledge gap. High ambient temperatures can be detrimental to the preservation of DNA, but refined methodology now allows data generation even from very poorly preserved samples. Here, we show for the first time that fish fossils from tropical lake sediments yield endogenous aDNA. Despite generally low endogenous content and high sample dropout, the application of high‐throughput sequencing and, in some cases, sequence capture allowed taxonomic assignment and phylogenetic placement of 17% of analysed fish fossils to family or tribe level, including remains which are up to 2700 years old or weigh less than 1 mg. The relationship between aDNA degradation and the thermal age of samples is similar to that described for terrestrial samples from cold environments when adjusted for elevated temperature. Success rates and aDNA preservation differed between the investigated lakes Chala, Kivu and Victoria, possibly caused by differences in bottom water oxygenation. Our study demonstrates that the sediment records of tropical lakes can preserve genetic information on rapidly diversifying fish taxa over time scales of millennia.

A review to frame the utilization of Eastern black walnut (Juglans nigra L.) cultivars in alley cropping systems - Benjamin Bishop; Nicholas A. Meier; Mark V. Coggeshall; Sarah T. Lovell; Ronald S. Revord (Agroforestry Systems, 2023)
Agroforestry adoptition is gaining considerable traction in the temperate US with growing popularity and government incentives (e.g., the Partnerships for Climate-Smart Commodities Project) for systems with greenhouse gas mitigation potential. The identification of complementary species combinations will accelerate the expansion of temperate agroforestry. Since the mid-19th century, European timber plantations have taken advantage of the late-leafing habit of walnut ( Juglans spp.) to grow a spring grain crop between the tree rows. Such alley cropping systems increase land-use efficiency and provide extensive environmental benefits. A parallel but underutilized opportunity in North American involves incorporating eastern black walnut ( Juglans nigra L.) cultivars into alley cropping systems (ACS). Eastern black walnut, henceforth referred to as black walnut, is native to North America and exhibits architectural and phenological characters for reduced competition with winter cereal crops grown in alleys. Black walnut also produces nutritious nuts, and cultivars with improved kernel percentage and mass offer potential to cultivate the species as a domesticated orchard crop, as opposed to just the high-quality timber for which it is well-known. However, field observations suggest significant variation in tree architecture and phenology amongst cultivars, which is likely to influence complementarity with winter grains. Comprehensive characterization of trait genetic diversity is needed to best leverage germplasm into productive systems. Here, we review literature related to implementing ACS with consideration of cultivar-dependent traits that may reduce interspecific competition. While the focus is directed toward black walnut, broad characterization of other underutilized fruit/nut species will allow for robust diversification of ACS.

Considerations for Water Temperature-Related Fishery Closures in Recreational Atlantic Salmon ( Salmo salar ) Catch and Release Fisheries: A Case Study from Eastern Canada - Travis E. Van Leeuwen; Sarah J. Lehnert; Cindy Breau; Michelle Fitzsimmons; Nicholas I. Kelly; J. Brian Dempson; Victoria M. Neville; Mark Young; Donald Keefe; Tomas J. Bird; David Cote (Reviews in Fisheries Science & Aquaculture, 2023)

Exposure considerations in human safety assessment: Report from an EPAA Partners’ Forum - Mark T.D. Cronin; Nicholas Ball; Sonja Beken; Hans Bender; Ofelia Bercaru; Laura Caneva; Marco Corvaro; Richard A. Currie; Jeffrey L. Dawson; Paul Desert; Sylvia E. Escher; Antonio Franco; et al. (Regulatory Toxicology and Pharmacology, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Distribution and trends of mercury in aquatic and terrestrial biota of New York, USA: a synthesis of 50 years of research and monitoring - Evan M. Adams; Julia E. Gulka; Yang Yang; Mark E. H. Burton; Douglas A. Burns; Valerie Buxton; Lisa Cleckner; Christopher R. DeSorbo; Charles T. Driscoll; David C. Evers; Nicholas Fisher; Oksana Lane; et al. (Ecotoxicology, 2023)

The impact of different fertiliser management options and cultivars on nitrogen use efficiency and yield for rice cropping in the Indo-Gangetic Plain: Two seasons of methane, nitrous oxide and ammonia emissions - Arti Bhatia; Nicholas J. Cowan; Julia Drewer; Ritu Tomer; Vinod Kumar; Shikha Sharma; Ankita Paul; Niveta Jain; Sandeep Kumar; Girish Jha; Renu Singh; Radha Prasanna; et al. (Agriculture, Ecosystems & Environment, 2023)

Observations of beach change and runup, and the performance of empirical runup parameterizations during large storm events - Lauren Nicole Kim; Katherine L. Brodie; Nicholas T. Cohn; Sarah N. Giddings; Mark Merrifield (Coastal Engineering, 2023)

OME-Zarr: a cloud-optimized bioimaging file format with international community support - Josh Moore; Daniela Basurto-Lozada; Sébastien Besson; John Bogovic; Jordão Bragantini; Eva M. Brown; Jean-Marie Burel; Xavier Casas Moreno; Gustavo de Medeiros; Erin E. Diel; David Gault; Satrajit S. Ghosh; et al. (Histochemistry and Cell Biology, 2023)
A growing community is constructing a next-generation file format (NGFF) for bioimaging to overcome problems of scalability and heterogeneity. Organized by the Open Microscopy Environment (OME), individuals and institutes across diverse modalities facing these problems have designed a format specification process (OME-NGFF) to address these needs. This paper brings together a wide range of those community members to describe the cloud-optimized format itself—OME-Zarr—along with tools and data resources available today to increase FAIR access and remove barriers in the scientific process. The current momentum offers an opportunity to unify a key component of the bioimaging domain—the file format that underlies so many personal, institutional, and global data management and analysis tasks.

Evaluation in a porcine wound model and long-term clinical assessment of an autologous heterogeneous skin construct used to close full-thickness wounds - Nicholas Baetz; Pratima Labroo; Marytheresa Ifediba; Devin Miller; Kendall Stauffer; Michael Sieverts; Jessie Nicodemus-Johnson; Eric Chan; Ian Robinson; James Miess; Stephanie Roth; Jenny Irvin; et al. (Tissue and Cell, 2023)

Antibody Fc-binding profiles and ACE2 affinity to SARS-CoV-2 RBD variants - Ebene R. Haycroft; Samantha K. Davis; Pradhipa Ramanathan; Ester Lopez; Ruth A. Purcell; Li Lynn Tan; Phillip Pymm; Bruce D. Wines; P. Mark Hogarth; Adam K. Wheatley; Jennifer A. Juno; Samuel J. Redmond; et al. (Medical Microbiology and Immunology, 2023)
Emerging SARS-CoV-2 variants, notably Omicron, continue to remain a formidable challenge to worldwide public health. The SARS-CoV-2 receptor-binding domain (RBD) is a hotspot for mutations, reflecting its critical role at the ACE2 interface during viral entry. Here, we comprehensively investigated the impact of RBD mutations, including 5 variants of concern (VOC) or interest—including Omicron (BA.2)—and 33 common point mutations, both on IgG recognition and ACE2-binding inhibition, as well as FcγRIIa- and FcγRIIIa-binding antibodies, in plasma from two-dose BNT162b2-vaccine recipients and mild-COVID-19 convalescent subjects obtained during the first wave using a custom-designed bead-based 39-plex array. IgG-recognition and FcγR-binding antibodies were decreased against the RBD of Beta and Omicron, as well as point mutation G446S, found in several Omicron sub-variants as compared to wild type. Notably, while there was a profound decrease in ACE2 inhibition against Omicron, FcγR-binding antibodies were less affected, suggesting that Fc functional antibody responses may be better retained against the RBD of Omicron in comparison to neutralization. Furthermore, while measurement of RBD–ACE2-binding affinity via biolayer interferometry showed that all VOC RBDs have enhanced affinity to human ACE2, we demonstrate that human ACE2 polymorphisms, E35K (rs1348114695) has reduced affinity to VOCs, while K26R (rs4646116) and S19P (rs73635825) have increased binding kinetics to the RBD of VOCs, potentially affecting virus–host interaction and, thereby, host susceptibility. Collectively, our findings provide in-depth coverage of the impact of RBD mutations on key facets of host–virus interactions.

Satellites reveal Earth's seasonally shifting dust emission sources - Adrian Chappell; Nicholas P. Webb; Mark Hennen; Kerstin Schepanski; Philippe Ciais; Yves Balkanski; Charles S. Zender; Ina Tegen; Zhenzhong Zeng; Daniel Tong; Barry Baker; Marie Ekström; et al. (Science of The Total Environment, 2023)

Development of a rapid and simple protocol for oil quantification of small (mg) mass oil seed samples - Ahmed AL. Bakri; Maythem AL. Amery; Kai Su; Robert Geneve; Mark Crocker; Nicholas Teets; Paul Armstrong; Pradeep Kachroo; David Hildebrand (Biocatalysis and Agricultural Biotechnology, 2023)

Genetic characterization of infectious spleen and kidney necrosis virus in Banggai cardinalfish Pterapogon kauderni identified from eight separate cases between 2000 and 2017 - Samantha A. Koda; Kuttichantran Subramaniam; Joseph M. Groff; Roy P. Yanong; Deborah B. Pouder; Matt Pedersen; Craig Pelton; Michael M. Garner; Nicholas B. D. Phelps; Anibal G. Armien; Michael W. Hyatt; Paul M. Hick; et al. (Journal of Fish Diseases, 2023)

Elevation-based probabilistic mapping of irregularly flooded wetlands along the northern Gulf of Mexico coast - Nicholas M. Enwright; Wyatt C. Cheney; Kristine O. Evans; Hana R. Thurman; Mark S. Woodrey; Auriel M.V. Fournier; Dean B. Gesch; Jonathan L. Pitchford; Jason M. Stoker; Stephen C. Medeiros (Remote Sensing of Environment, 2023)

Applying genetic technologies to combat infectious diseases in aquaculture - Nicholas A. Robinson; Diego Robledo; Lene Sveen; Rose Ruiz Daniels; Aleksei Krasnov; Andrew Coates; Ye Hwa Jin; Luke T. Barrett; Marie Lillehammer; Anne H. Kettunen; Ben L. Phillips; Tim Dempster; et al. (Reviews in Aquaculture, 2023)
Disease and parasitism cause major welfare, environmental and economic concerns for global aquaculture. In this review, we examine the status and potential of technologies that exploit genetic variation in host resistance to tackle this problem. We argue that there is an urgent need to improve understanding of the genetic mechanisms involved, leading to the development of tools that can be applied to boost host resistance and reduce the disease burden. We draw on two pressing global disease problems as case studies—sea lice infestations in salmonids and white spot syndrome in shrimp. We review how the latest genetic technologies can be capitalised upon to determine the mechanisms underlying inter‐ and intra‐species variation in pathogen/parasite resistance, and how the derived knowledge could be applied to boost disease resistance using selective breeding, gene editing and/or with targeted feed treatments and vaccines. Gene editing brings novel opportunities, but also implementation and dissemination challenges, and necessitates new protocols to integrate the technology into aquaculture breeding programmes. There is also an ongoing need to minimise risks of disease agents evolving to overcome genetic improvements to host resistance, and insights from epidemiological and evolutionary models of pathogen infestation in wild and cultured host populations are explored. Ethical issues around the different approaches for achieving genetic resistance are discussed. Application of genetic technologies and approaches has potential to improve fundamental knowledge of mechanisms affecting genetic resistance and provide effective pathways for implementation that could lead to more resistant aquaculture stocks, transforming global aquaculture.

Correction to: Performance of structures with clutch inerter dampers subjected to seismic excitation - Peter C. Talley; Anika T. Sarkar; Nicholas E. Wierschem; Mark D. Denavit (Bulletin of Earthquake Engineering, 2023)

Performance of structures with clutch inerter dampers subjected to seismic excitation - Peter C. Talley; Anika T. Sarkar; Nicholas E. Wierschem; Mark D. Denavit (Bulletin of Earthquake Engineering, 2023)

A framework for a net environmental benefit analysis based comparative assessment of decommissioning options for anthropogenic subsea structures: A North Sea case study - Joseph P. Nicolette; Nicholas A. Nelson; Michael K. Rockel; Mark L. Rockel; Alex N. Testoff; Larry L. Johnson; Laura D. Williamson; Victoria L. G. Todd (Frontiers in Marine Science, 2023)
Taxpayers and operators worldwide have significant current liabilities associated with decommissioning of offshore Oil & Gas (O&G) assets. Consequently, decommissioning is at the forefront of industrial, governmental, and non-governmental agendas. Decommissioning is a highly complex activity with health, safety, environmental, social, economic, and technical implications. Increasing scientific evidence supports that manmade subsea structures create hard, artificial reef habitats that provide ecological and social benefits to society. Given the significant uncertainty regarding how subsea structures should be retired at the end of their operational lifetimes, it is necessary for governments, taxpayers, and operators to understand the risks and benefits associated with potential decommissioning options. Currently, the North Sea decommissioning process is based on the policies and direction of the Oslo and Paris Convention’s (OSPAR) Decision 98/3 and follow comparative assessment (CA) multiple-criteria decision analysis (MCDA) guidelines to determine the best overall strategy for decommissioning subsea structures; however, CA MCDA processes can be biased, ambiguous, difficult to use, interpret, and replicate, and limited in their consideration of multigenerational benefits. Consequently, to assist decision-makers in understanding and evaluating options and associated benefits for decommissioning subsea structures, this study adapted the net environmental benefit analysis (NEBA) framework to supplement and strengthen the CA process for evaluating decommissioning options for offshore O&G facilities. The net environmental benefit analysis based comparative assessment (NEBA-CA) framework is presented that addresses the growing need for a practical, quantitative, scientifically robust, defendable, and transparent MCDA approach to determine optimized decommissioning strategies for subsea assets. Increased transparency in CAs will provide an additional layer of credibility with regulators and society. The approach is data driven and a desktop analysis mainly relying on existing data. Using a North Sea case study, this work demonstrates the ability of NEBA-CA to resolve inherent complexity in comparing decommissioning options, thereby supporting operators in working with regulators to decommission assets in a way that maximizes ecosystem service benefits to society while managing site-related risks and costs. The NEBA-CA framework supplements and strengthens the standard CA process by 1) incorporating quantified metrics including multigenerational ecosystem service benefits and risks, 2) excluding front ranking (scoring) or weighting of metrics, and 3) providing consistent graphical displays to support visual differentiation of options and metrics.

A life cycle model for evaluating estuary residency and recovery potential in Chinook salmon - Emily K. Chen; Nicholas A. Som; John D. Deibner-Hanson; David G. Anderson; Mark J. Henderson (Fisheries Research, 2023)

Greenhouse gas mitigation potential in smallholder agroecosystem of southern Ethiopia - Bekele Lemma; Paul H. Evangelista; Mathew Stermer; Nicholas E. Young; Eleanor Milne; Mark Easter (Journal of Environmental Management, 2023)

Leave No Trace? Ecological and anthropogenic determinants of antibiotic resistant bacteria in a recreational alpine environment - Laura C. Scott; Alexandra Aubee; Mark J. Wilson; Scott Esser; Denisse Descamps; Nicholas Lee; Emiko Distler; Tiong Gim Aw (Environmental Research, 2023)

Modelled direct causes of dust emission change (2001–2020) in southwestern USA and implications for management - Mark Hennen; Adrian Chappell; Nicholas P. Webb (Aeolian Research, 2023)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Effects of climate change on forest plantation productivity in Chile - Gonzalo Carrasco; Auro C. Almeida; Mark Falvey; Guillermo Federico Olmedo; Peter Taylor; Fernando Santibañez; Nicholas C. Coops (Global Change Biology, 2022)
Forest plantations in Chile occupy more than 2.2 million ha and are responsible for 2.1% of the GDP of the country's economy. The ability to accurately predictions of plantations productivity under current and future climate has an impact can enhance on forest management and industrial wood production. The use of process‐based models to predict forest growth has been instrumental in improving the understanding and quantifying the effects of climate variability, climate change, and the impact of atmospheric CO 2 concentration and management practices on forest growth. This study uses the 3‐PG model to predict future forest productivity Eucalyptus globulus and Pinus radiata . The study integrates climate data from global circulation models used in CMIP5 for scenarios RCP26 and RCP85, digital soil maps for physical and chemical variables. Temporal and spatial tree growth inventories were used to compare with the 3‐PG predictions. The results indicated that forest productivity is predicted to potentially increase stand volume (SV) over the next 50 years by 26% and 24% for the RCP26 scenario and between 73% and 62% for the RCP85 scenario for E. globulus and P. radiata , respectively. The predicted increases can be explained by a combination of higher level of atmospheric CO 2 , air temperatures closer to optimum than current, and increases in tree water use efficiency. If the effect of CO 2 is not considered, the predicted differences of SV for 2070 are 16% and 14% for the RCP26 scenario and 22% and 14% for RCP85 for the two species. While shifts in climate and increasing CO 2 are likely to benefit promote higher productivity, other factors such as lack insufficient availability of soil nutrients, events such as increasing frequency and duration of droughts, longer periods of extreme temperatures, competing vegetation, and occurrence of new pests and diseases may compromise these potential gains.

In Silico Development of Combinatorial Therapeutic Approaches Targeting Key Signaling Pathways in Metabolic Syndrome - Maksim Khotimchenko; Nicholas E. Brunk; Mark S. Hixon; Daniel M. Walden; Hypatia Hou; Kaushik Chakravarty; Jyotika Varshney (Pharmaceutical Research, 2022)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

A systematic review and meta-analysis of non-vitamin K antagonist oral anticoagulants vs vitamin K antagonists after transcatheter aortic valve replacement in patients with atrial fibrillation - Amanda Jia Qi Ooi; Chloe Wong; Timothy Wei Ern Tan; Trina Priscilla Ng; Yao Neng Teo; Yao Hao Teo; Nicholas L. Syn; Andie H. Djohan; Yinghao Lim; Leonard L. L. Yeo; Benjamin Y. Q. Tan; Mark Yan-Yee Chan; et al. (European Journal of Clinical Pharmacology, 2022)

Integrating blue: How do we make nationally determined contributions work for both blue carbon and local coastal communities? - Amrit Melissa Dencer-Brown; Robyn Shilland; Daniel Friess; Dorothée Herr; Lisa Benson; Nicholas J. Berry; Miguel Cifuentes-Jara; Patrick Colas; Ellyn Damayanti; Elisa López García; Marina Gavaldão; Gabriel Grimsditch; et al. (Ambio, 2022)
Blue Carbon Ecosystems (BCEs) help mitigate and adapt to climate change but their integration into policy, such as Nationally Determined Contributions (NDCs), remains underdeveloped. Most BCE conservation requires community engagement, hence community-scale projects must be nested within the implementation of NDCs without compromising livelihoods or social justice. Thirty-three experts, drawn from academia, project development and policy, each developed ten key questions for consideration on how to achieve this. These questions were distilled into ten themes, ranked in order of importance, giving three broad categories of people , policy & finance , and science & technology . Critical considerations for success include the need for genuine participation by communities, inclusive project governance, integration of local work into national policies and practices, sustaining livelihoods and income (for example through the voluntary carbon market and/or national Payment for Ecosystem Services and other types of financial compensation schemes) and simplification of carbon accounting and verification methodologies to lower barriers to entry.

Parasitism of urban bumble bees influenced by pollinator taxonomic richness, local garden management, and surrounding impervious cover - Nicholas A. Ivers; Zacchariah Jordan; Hamutahl Cohen; Amber Tripodi; Mark J. F. Brown; Heidi Liere; Brenda B. Lin; Stacy Philpott; Shalene Jha (Urban Ecosystems, 2022)

An effector index to predict target genes at GWAS loci - Vincenzo Forgetta; Lai Jiang; Nicholas A. Vulpescu; Megan S. Hogan; Siyuan Chen; John A. Morris; Stepan Grinek; Christian Benner; Dong-Keun Jang; Quy Hoang; Noel Burtt; Jason A. Flannick; et al. (Human Genetics, 2022)

Climate impacts alter fisheries productivity and turnover on coral reefs - Mark Hamilton; James P. W. Robinson; Cassandra E. Benkwitt; Shaun K. Wilson; M. Aaron MacNeil; Ameer Ebrahim; Nicholas A. J. Graham (Coral Reefs, 2022)
Alteration of benthic reef habitat after coral bleaching and mortality induces changes in fish assemblages, with implications for fisheries. Our understanding of climate impacts to coral reef fisheries is largely based on fish abundance and biomass. The rates at which biomass is produced and replenished (productivity and turnover) are also important to sustaining fisheries, yet the responses of these metrics following bleaching are largely unknown. Here, we examine changes in fish productivity and turnover after mass coral bleaching events in Seychelles, on reefs that were recovering to coral-dominated habitats and those that shifted to macroalgae-dominated regimes. Productivity of fish assemblages increased on all recovering reefs, particularly on fished reefs resulting in levels similar to protected reefs 19 years after bleaching. Herbivore-detritivores, such as scraping and excavating parrotfish, appeared to drive biomass production through increased abundance on recovering reefs. Productivity on regime-shifted reefs remained stable at 1994 levels in fished areas, with increases observed on protected reefs. Large increases in browser productivity (particularly on protected reefs), combined with increases for invertivores, maintained post-bleaching productivity on macroalgal reefs. For all diet groups, net turnover was generally higher on fished regime-shifted reefs than on recovering reefs, suggesting fish biomass is more readily replenished on macroalgal reefs. Reef structural complexity was a positive predictor of productivity for all diet groups. These findings indicate that post-bleaching reef fish productivity is strongly influenced by benthic recovery trajectories, and demonstrates the importance of herbivore and invertivore species in sustaining small-scale inshore fisheries following climatic disturbances.

Delineation of blacktip shark ( Carcharhinus limbatus ) nursery habitats in the north‐western Gulf of Mexico - Philip Matich; Camryn L. Bigelow; Barrett Chambers; Jillian J. Dodds; Jessica A. Hebert; Alexis Lemieux; Christy M. Pittman; Julianna Trapp; Brooke Bianco; Carolina P. Cadena; Emily I. Castillo; Gabriela I. Castillo; et al. (Journal of Fish Biology, 2022)
Coevolution with predators leads to the use of low‐risk habitats by many prey species, which promotes survival during early developmental phases. These nurseries are valued by conservation and management agencies because of their contributions to adult populations. However, the physical and geographic characteristics, like shallow depths and isolation from other marine habitats, that restrict access to predators and thereby reduce risk to juvenile animals can also limit scientific research. Consequently, many nursery habitats are still unidentified and understudied. Here we used gillnet monitoring from 1982 to 2018 to delineate blacktip shark ( Carcharhinus limbatus ) nurseries in the north‐western Gulf of Mexico and elucidated their physical, environmental and biological characteristics. Nursery habitats within estuaries (

Designing and managing biodiverse streetscapes: key lessons from the City of Melbourne - Hui-Anne Tan; Lee Harrison; Jeff Nelson; Maggie Lokic; John P. Rayner; Caragh G. Threlfall; Jessica Baumann; Adrian Marshall; Mark Callow; Jessica Peeler; Rebecca Korossy-Horwood; Chris Nicholson; et al. (Urban Ecosystems, 2022)

Evaluation of a blood-based geroscience biomarker index in a randomized trial of caloric restriction and exercise in older adults with heart failure with preserved ejection fraction - Jamie N. Justice; Nicholas M. Pajewski; Mark A. Espeland; Peter Brubaker; Denise K. Houston; Santica Marcovina; Barbara J. Nicklas; Stephen B. Kritchevsky; Dalane W. Kitzman (GeroScience, 2022)

A framework for chemical safety assessment incorporating new approach methodologies within REACH - Nicholas Ball; Remi Bars; Philip A. Botham; Andreea Cuciureanu; Mark T. D. Cronin; John E. Doe; Tatsiana Dudzina; Timothy W. Gant; Marcel Leist; Bennard van Ravenzwaay (Archives of Toxicology, 2022)
The long-term investment in new approach methodologies (NAMs) within the EU and other parts of the world is beginning to result in an emerging consensus of how to use information from in silico, in vitro and targeted in vivo sources to assess the safety of chemicals. However, this methodology is being adopted very slowly for regulatory purposes. Here, we have developed a framework incorporating in silico , in vitro and in vivo methods designed to meet the requirements of REACH in which both hazard and exposure can be assessed using a tiered approach. The outputs from each tier are classification categories, safe doses, and risk assessments, and progress through the tiers depends on the output from previous tiers. We have exemplified the use of the framework with three examples. The outputs were the same or more conservative than parallel assessments based on conventional studies. The framework allows a transparent and phased introduction of NAMs in chemical safety assessment and enables science-based safety decisions which provide the same level of public health protection using fewer animals, taking less time, and using less financial and expert resource. Furthermore, it would also allow new methods to be incorporated as they develop through continuous selective evolution rather than periodic revolution.

Biosecurity and the ornamental fish trade: A stakeholder perspective in England - Louisa E. Wood; James Guilder; Marnie L. Brennan; Nicola J. Birland; Virginia Taleti; Nicholas Stinton; Nick G. H. Taylor; Mark A. Thrush (Journal of Fish Biology, 2022)
The freshwater and marine ornamental fish industry is a primary route of hazard introduction and emergence, including aquatic animal diseases and non‐native species. Prevention measures are key to reducing the risk of hazard incursion and establishment, but there is currently little understanding of the biosecurity practices and hazard responses implemented at post‐border stages of the ornamental fish supply chain. This study addresses this knowledge gap, using questionnaires to collate information on actual biosecurity behaviours and hazard responses practised by ornamental fish retailers and hobbyist communities in England. Actual behaviours varied considerably within retailers and hobbyists, suggesting that reliance on preventative practices by individuals in the post‐border stages of the ornamental fish supply chain is likely to be ineffective in minimizing the risk of hazard incursion and establishment. Resources should be allocated towards improving and enforcing robust pre‐ and at‐border control measures, such as risk‐based surveillance of ornamental fish imports at border controls. In addition, these findings should be used to implement targeted awareness‐raising campaigns and help create directed training on biosecurity practices for individuals involved in the post‐border stages of the ornamental supply chain.

Promoting FAIR Data Through Community-driven Agile Design: the Open Data Commons for Spinal Cord Injury (odc-sci.org) - Abel Torres-Espín; Carlos A. Almeida; Austin Chou; J. Russell Huie; Michael Chiu; Romana Vavrek; Jeff Sacramento; Michael B. Orr; John C. Gensel; Jeffery S. Grethe; Maryann E. Martone; Karim Fouad; et al. (Neuroinformatics, 2022)
The past decade has seen accelerating movement from data protectionism in publishing toward open data sharing to improve reproducibility and translation of biomedical research. Developing data sharing infrastructures to meet these new demands remains a challenge. One model for data sharing involves simply attaching data, irrespective of its type, to publisher websites or general use repositories. However, some argue this creates a ‘data dump’ that does not promote the goals of making data Findable, Accessible, Interoperable and Reusable (FAIR). Specialized data sharing communities offer an alternative model where data are curated by domain experts to make it both open and FAIR. We report on our experiences developing one such data-sharing ecosystem focusing on ‘long-tail’ preclinical data, the Open Data Commons for Spinal Cord Injury (odc-sci.org). ODC-SCI was developed with community-based agile design requirements directly pulled from a series of workshops with multiple stakeholders (researchers, consumers, non-profit funders, governmental agencies, journals, and industry members). ODC-SCI focuses on heterogeneous tabular data collected by preclinical researchers including bio-behaviour, histopathology findings and molecular endpoints. This has led to an example of a specialized neurocommons that is well-embraced by the community it aims to serve. In the present paper, we provide a review of the community-based design template and describe the adoption by the community including a high-level review of current data assets, publicly released datasets, and web analytics. Although odc-sci.org is in its late beta stage of development, it represents a successful example of a specialized data commons that may serve as a model for other fields.

Wave exposure shapes reef community composition and recovery trajectories at a remote coral atoll - Ines D. Lange; Cassandra E. Benkwitt; Jamie M. McDevitt-Irwin; Kristina L. Tietjen; Brett Taylor; Mark Chinkin; Rachel L. Gunn; Melissa Palmisciano; Margaux Steyaert; Bry Wilson; Holly K. East; John Turner; et al. (Coral Reefs, 2021)
In a time of unprecedented ecological change, understanding natural biophysical relationships between reef resilience and physical drivers is of increasing importance. This study evaluates how wave forcing structures coral reef benthic community composition and recovery trajectories after the major 2015/2016 bleaching event in the remote Chagos Archipelago, Indian Ocean. Benthic cover and substrate rugosity were quantified from digital imagery at 23 fore reef sites around a small coral atoll (Salomon) in 2020 and compared to data from a similar survey in 2006 and opportunistic surveys in intermediate years. Cluster analysis and principal component analysis show strong separation of community composition between exposed (modelled wave exposure > 1000 J m −3 ) and sheltered sites (< 1000 J m −3 ) in 2020. This difference is driven by relatively high cover of Porites sp., other massive corals, encrusting corals, soft corals, rubble and dead table corals at sheltered sites versus high cover of pavement and sponges at exposed sites. Total coral cover and rugosity were also higher at sheltered sites. Adding data from previous years shows benthic community shifts from distinct exposure-driven assemblages and high live coral cover in 2006 towards bare pavement, dead Acropora tables and rubble after the 2015/2016 bleaching event. The subsequent recovery trajectories at sheltered and exposed sites are surprisingly parallel and lead communities towards their respective pre-bleaching communities. These results demonstrate that in the absence of human stressors, community patterns on fore reefs are strongly controlled by wave exposure, even during and after widespread coral loss from bleaching events.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Magnitude, Scale, and Dynamics of the 2020 Mei-yu Rains and Floods over China - Ambrogio Volonté; Mark Muetzelfeldt; Reinhard Schiemann; Andrew G. Turner; Nicholas Klingaman (Advances in Atmospheric Sciences, 2021)
Large parts of East and South Asia were affected by heavy precipitation and flooding during early summer 2020. This study provides both a statistical and dynamical characterization of rains and floods affecting the Yangtze River Basin (YRB). By aggregating daily and monthly precipitation over river basins across Asia, it is shown that the YRB is one of the areas that was particularly affected. June and July 2020 rainfall was higher than in the previous 20 years, and the YRB experienced anomalously high rainfall across most of its sub-basins. YRB discharge also attained levels not seen since 1998/1999. An automated method detecting the daily position of the East Asian Summer Monsoon Front (EASMF) is applied to show that the anomalously high YRB precipitation was associated with a halted northward progression of the EASMF and prolonged mei-yu conditions over the YRB lasting more than one month. Two 5-day heavy-precipitation episodes (12−16 June and 4−8 July 2020) are selected from this period for dynamical characterization, including Lagrangian trajectory analysis. Particular attention is devoted to the dynamics of the airstreams converging at the EASMF. Both episodes display heavy precipitation and convergence of monsoonal and subtropical air masses. However, clear differences are identified in the upper-level flow pattern, substantially affecting the balance of airmass advection towards the EASMF. This study contextualizes heavy precipitation in Asia in summer 2020 and showcases several analysis tools developed by the authors for the study of such events.

Considering Commercial Vessels as Potential Vectors of Stony Coral Tissue Loss Disease - Nicholas A. Rosenau; Sarah Gignoux-Wolfsohn; Richard A. Everett; A. Whitman Miller; Mark S. Minton; Gregory M. Ruiz (Frontiers in Marine Science, 2021)
Stony coral tissue loss disease (SCTLD) is a troubling new disease that is spreading rapidly across the greater Caribbean region, but the etiological agent(s) and the mechanisms(s) of spread are both unknown. First detected off the coast of Miami, Florida, major ocean currents alone do not explain the pattern of spread, with outbreaks occurring across geographically disjunct and distant locations. This has raised concerns by researchers and resource managers that commercial vessels may contribute as vectors to spread of the disease. Despite existing regulatory and management strategies intended to limit coastal marine invasion risks, the efficacy of these measures is still unresolved for ship-borne microorganisms, and disease transport via ballast water and hull biofouling are under examination given the high ship traffic in the region. Here, to help inform the discussion of ships as possible vectors of SCTLD, we provide an overview of the current state of knowledge about ships and their potential to transfer organisms in the greater Caribbean, focusing in particular on ballast water, and outline a set of recommendations for future research.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Wetland Selection by Female Ring-Necked Ducks (Aythya collaris) in the Southern Atlantic Flyway - Tori D. Mezebish; Richard B. Chandler; Glenn H. Olsen; Michele Goodman; Frank C. Rohwer; Nicholas J. Meng; Mark D. McConnell (Wetlands, 2021)

Pattern, style and timing of British–Irish Ice Sheet retreat: Shetland and northern North Sea sector - Tom Bradwell; David Small; Derek Fabel; Chris D. Clark; Richard C. Chiverrell; Margot H. Saher; Dayton Dove; S. Louise Callard; Matthew J. Burke; Steven G. Moreton; Alicia Medialdea; Mark D. Bateman; et al. (Journal of Quaternary Science, 2021)
The offshore sector around Shetland remains one of the least well‐studied parts of the former British–Irish Ice Sheet with several long‐standing scientific issues unresolved. These key issues include (i) the dominance of a locally sourced ‘Shetland ice cap’ vs an invasive Fennoscandian Ice Sheet; (ii) the flow configuration and style of glaciation at the Last Glacial Maximum (i.e. terrestrial vs marine glaciation); (iii) the nature of confluence between the British–Irish and Fennoscandian Ice Sheets; (iv) the cause, style and rate of ice sheet separation; and (v) the wider implications of ice sheet uncoupling on the tempo of subsequent deglaciation. As part of the Britice‐Chrono project, we present new geological (seabed cores), geomorphological, marine geophysical and geochronological data from the northernmost sector of the last British–Irish Ice Sheet (north of 59.5°N) to address these questions. The study area covers ca. 95 000 km 2 , an area approximately the size of Ireland, and includes the islands of Shetland and the surrounding continental shelf, some of the continental slope, and the western margin of the Norwegian Channel. We collect and analyse data from onshore in Shetland and along key transects offshore, to establish the most coherent picture, so far, of former ice‐sheet deglaciation in this important sector. Alongside new seabed mapping and Quaternary sediment analysis, we use a multi‐proxy suite of new isotopic age assessments, including 32 cosmogenic‐nuclide exposure ages from glacially transported boulders and 35 radiocarbon dates from deglacial marine sediments, to develop a synoptic sector‐wide reconstruction combining strong onshore and offshore geological evidence with Bayesian chronosequence modelling. The results show widespread and significant spatial fluctuations in size, shape and flow configuration of an ice sheet/ice cap centred on, or to the east of, the Orkney–Shetland Platform, between ~30 and ~15 ka BP. At its maximum extent ca. 26–25 ka BP , this ice sheet was coalescent with the Fennoscandian Ice Sheet to the east. Between ~25 and 23 ka BP the ice sheet in this sector underwent a significant size reduction from ca. 85 000 to 2 , accompanied by several ice‐margin oscillations. Soon after, connection was lost with the Fennoscandian Ice Sheet and a marine corridor opened to the east of Shetland. This triggered initial (and unstable) re‐growth of a glaciologically independent Shetland Ice Cap ca. 21–20 ka BP with a strong east–west asymmetry with respect to topography. Ice mass growth was followed by rapid collapse, from an area of ca. 45 000 km 2 to ca. 15 000 km 2 between 19 and 18 ka BP , stabilizing at ca. 2000 km 2 by ~17 ka BP. Final deglaciation of Shetland occurred ca. 17–15 ka BP , and may have involved one or more subsidiary ice centres on now‐submerged parts of the continental shelf. We suggest that the unusually dynamic behaviour of the northernmost sector of the British–Irish Ice Sheet between 21 and 18 ka BP – characterized by numerous extensive ice sheet/ice mass readvances, rapid loss and flow redistributions – was driven by significant changes in ice mass geometry, ice divide location and calving flux as the glaciologically independent ice cap adjusted to new boundary conditions. We propose that this dynamism was forced to a large degree by internal (glaciological) factors specific to the strongly marine‐influenced Shetland Ice Cap.

Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

Meeting Paris agreement objectives will temper seabird winter distribution shifts in the North Atlantic Ocean - Manon Clairbaux; William W. L. Cheung; Paul Mathewson; Warren Porter; Nicolas Courbin; Jérôme Fort; Hallvard Strøm; Børge Moe; Per Fauchald; Sebastien Descamps; Hálfdán Helgason; Vegard S. Bråthen; et al. (Global Change Biology, 2021)
We explored the implications of reaching the Paris Agreement Objective of limiting global warming to Alle alle , Fratercula arctica , Uria aalge , Uria lomvia and Rissa tridactyla ) using tracking data for ~1500 individuals through resource selection functions based on mechanistic modeling of seabird energy requirements, and a dynamic bioclimate envelope model of seabird prey. Future winter distributions were predicted to shift with climate change, especially when global warming exceed 2°C under a “no mitigation” scenario, modifying seabird wintering hotspots in the North Atlantic Ocean. Our findings suggest that meeting Paris agreement objectives will limit changes in seabird selected habitat location and size in the North Atlantic Ocean during the 21st century. We thereby provide key information for the design of adaptive marine‐protected areas in a changing ocean.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

The Fate of Deep-Sea Coral Reefs on Seamounts in a Fishery-Seascape: What Are the Impacts, What Remains, and What Is Protected? - Alan Williams; Franziska Althaus; Kylie Maguire; Mark Green; Candice Untiedt; Phil Alderslade; Malcolm R. Clark; Nicholas Bax; Thomas A. Schlacher (Frontiers in Marine Science, 2020)

Emergence of negative affect as motivation for drug taking in rats chronically self-administering cocaine - Samuel D. Klein; Nicholas J. Beacher; Julianna M. Kulik; David J. Estrin; Anthony P. Pawlak; Mark O. West (Psychopharmacology, 2020)

Brightness of the Night Sky Affects Loggerhead (Caretta caretta) Sea Turtle Hatchling Misorientation but Not Nest Site Selection - Thomas R. Stanley; Jeremy M. White; Susan Teel; Mark Nicholas (Frontiers in Marine Science, 2020)

True Size Matters for Conservation: A Robust Method to Determine the Size of Deep-Sea Coral Reefs Shows They Are Typically Small on Seamounts in the Southwest Pacific Ocean - Alan Williams; Franziska Althaus; Mark Green; Kylie Maguire; Candice Untiedt; Nick Mortimer; Chris J. Jackett; Malcolm Clark; Nicholas Bax; Roland Pitcher; Thomas Schlacher (Frontiers in Marine Science, 2020)

Synchronous biological feedbacks in parrotfishes associated with pantropical coral bleaching - Brett M. Taylor; Cassandra E. Benkwitt; Howard Choat; Kendall D. Clements; Nicholas A. J. Graham; Mark G. Meekan (Global Change Biology, 2020)
Biological feedbacks generated through patterns of disturbance are vital for sustaining ecosystem states. Recent ocean warming and thermal anomalies have caused pantropical episodes of coral bleaching, which has led to widespread coral mortality and a range of subsequent effects on coral reef communities. Although the response of many reef‐associated fishes to major disturbance events on coral reefs is negative (e.g., reduced abundance and condition), parrotfishes show strong feedbacks after disturbance to living reef structure manifesting as increases in abundance. However, the mechanisms underlying this response are poorly understood. Using biochronological reconstructions of annual otolith (ear stone) growth from two ocean basins, we tested whether parrotfish growth was enhanced following bleaching‐related coral mortality, thus providing an organismal mechanism for demographic changes in populations. Both major feeding guilds of parrotfishes (scrapers and excavators) exhibited enhanced growth of individuals after bleaching that was decoupled from expected thermal performance, a pattern that was not evident in other reef fish taxa from the same environment. These results provide evidence for a more nuanced ecological feedback system—one where disturbance plays a key role in mediating parrotfish–benthos interactions. By influencing the biology of assemblages, disturbance can thereby stimulate change in parrotfish grazing intensity and ultimately reef geomorphology over time. This feedback cycle operated historically at within‐reef scales; however, our results demonstrate that the scale, magnitude, and severity of recent thermal events are entraining the biological responses of disparate communities to respond in synchrony. This may fundamentally alter feedbacks in the relationships between parrotfishes and reef systems.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Water stress tolerance tracks environmental exposure and exhibits a fluctuating sexual dimorphism in a tropical liverwort - Rose A. Marks; Brennen D. Pike; D. Nicholas McLetchie (Oecologia, 2019)

To pool or not to pool? Guidelines for pooling samples for use in surveillance testing of infectious diseases in aquatic animals - Emilie Laurin; Krishna Thakur; Peter G. Mohr; Paul Hick; Mark St. J. Crane; Ian A. Gardner; Nicholas J. G. Moody; Axel Colling; Ingo Ernst (Journal of Fish Diseases, 2019)
Samples from multiple animals may be pooled and tested to reduce costs of surveillance for infectious agents in aquatic animal populations. The primary advantage of pooling is increased population‐level coverage when prevalence is low (

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

Evolving and Sustaining Ocean Best Practices and Standards for the Next Decade - Jay Pearlman; Mark Bushnell; Laurent Coppola; Johannes Karstensen; Pier Luigi Buttigieg; Francoise Pearlman; Pauline Simpson; Michele Barbier; Frank E. Muller-Karger; Cristian Munoz-Mas; Peter Pissierssens; Cyndy Chandler; et al. (Frontiers in Marine Science, 2019)

The Role of Stakeholders in Creating Societal Value From Coastal and Ocean Observations - Bev Mackenzie; Louis Celliers; Luiz Paulo de Freitas Assad; Johanna J. Heymans; Nicholas Rome; Julie Thomas; Clarissa Anderson; James Behrens; Mark Calverley; Kruti Desai; Paul M. DiGiacomo; Samy Djavidnia; et al. (Frontiers in Marine Science, 2019)

New shock microstructures in titanite (CaTiSiO5) from the peak ring of the Chicxulub impact structure, Mexico - Nicholas E. Timms; Mark A. Pearce; Timmons M. Erickson; Aaron J. Cavosie; Auriol S. P. Rae; John Wheeler; Axel Wittmann; Ludovic Ferrière; Michael H. Poelchau; Naotaka Tomioka; Gareth S. Collins; Sean P. S. Gulick; et al. (Contributions to Mineralogy and Petrology, 2019)

Globally Consistent Quantitative Observations of Planktonic Ecosystems - Fabien Lombard; Emmanuel Boss; Anya M. Waite; Meike Vogt; Julia Uitz; Lars Stemmann; Heidi M. Sosik; Jan Schulz; Jean-Baptiste Romagnan; Marc Picheral; Jay Pearlman; Mark D. Ohman; et al. (Frontiers in Marine Science, 2019)

Fluorescent reporter transgenic mice for in vivo live imaging of angiogenesis and lymphangiogenesis - Susan J. Doh; Michael Yamakawa; Samuel M. Santosa; Mario Montana; Kai Guo; Joseph R. Sauer; Nicholas Curran; Kyu-Yeon Han; Charles Yu; Masatsugu Ema; Mark I. Rosenblatt; Jin-Hong Chang; et al. (Angiogenesis, 2018)

The effects of multi-stage exercise with and without concurrent cognitive performance on cardiorespiratory and cerebral haemodynamic responses - David Stevens; Mark Halaki; Chin Moi Chow; Nicholas O’Dwyer (European Journal of Applied Physiology, 2018)

Advancing Marine Biological Observations and Data Requirements of the Complementary Essential Ocean Variables (EOVs) and Essential Biodiversity Variables (EBVs) Frameworks - Frank E. Muller-Karger; Patricia Miloslavich; Nicholas J. Bax; Samantha Simmons; Mark J. Costello; Isabel Sousa Pinto; Gabrielle Canonico; Woody Turner; Michael Gill; Enrique Montes; Benjamin D. Best; Jay Pearlman; et al. (Frontiers in Marine Science, 2018)

Tau Phosphorylation is Impacted by Rare AKAP9 Mutations Associated with Alzheimer Disease in African Americans - Tsuneya Ikezu; Cidi Chen; Annina M. DeLeo; Ella Zeldich; M. Daniele Fallin; Nicholas M. Kanaan; Kathryn L. Lunetta; Carmela R. Abraham; Mark W. Logue; Lindsay A. Farrer (Journal of Neuroimmune Pharmacology, 2018)

Variation in the bacteriome of the tropical liverwort, Marchantia inflexa, between the sexes and across habitats - Rose A. Marks; Jeramiah J. Smith; Quentin Cronk; D. Nicholas McLetchie (Symbiosis, 2018)

Improvement to the Convergence-Confinement Method: Inclusion of Support Installation Proximity and Stiffness - Jeffrey Oke; Nicholas Vlachopoulos; Mark Diederichs (Rock Mechanics and Rock Engineering, 2018)

Combining abundance and performance data reveals how temperature regulates coastal occurrences and activity of a roaming apex predator - Nicholas L. Payne; Carl G. Meyer; James A. Smith; Jonathan D. R. Houghton; Adam Barnett; Bonnie J. Holmes; Itsumi Nakamura; Yannis P. Papastamatiou; Mark A. Royer; Daniel M. Coffey; James M. Anderson; Melanie R. Hutchinson; et al. (Global Change Biology, 2018)
The redistribution of species has emerged as one of the most pervasive impacts of anthropogenic climate warming, and presents many societal challenges. Understanding how temperature regulates species distributions is particularly important for mobile marine fauna such as sharks given their seemingly rapid responses to warming, and the socio‐political implications of human encounters with some dangerous species. The predictability of species distributions can potentially be improved by accounting for temperature's influence on performance, an elusive relationship for most large animals. We combined multi‐decadal catch data and bio‐logging to show that coastal abundance and swimming performance of tiger sharks Galeocerdo cuvier are both highest at ~22°C, suggesting thermal constraints on performance may regulate this species' distribution. Tiger sharks are responsible for a large proportion of shark bites on humans, and a focus of controversial control measures in several countries. The combination of distribution and performance data moves towards a mechanistic understanding of tiger shark's thermal niche, and delivers a simple yet powerful indicator for predicting the location and timing of their occurrences throughout coastlines. For example, tiger sharks are mostly caught at Australia's popular New South Wales beaches (i.e. near Sydney) in the warmest months, but our data suggest similar abundances will occur in winter and summer if annual sea surface temperatures increase by a further 1–2°C.

Starting a Medical Technology Venture as a Young Academic Innovator or Student Entrepreneur - Amir Manbachi; Katlin Kreamer-Tonin; Philipp Walch; Nao J. Gamo; Parastoo Khoshakhlagh; Yu Shrike Zhang; Charles Montague; Soumyadipta Acharya; Elizabeth A. Logsdon; Robert H. Allen; Nicholas J. Durr; Mark G. Luciano; et al. (Annals of Biomedical Engineering, 2018)

Integration of Lidar-Based Structural Input and Discrete Fracture Network Generation for Underground Applications - Ioannis Vazaios; Nicholas Vlachopoulos; Mark S. Diederichs (Geotechnical and Geological Engineering, 2017)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

“The river is us; the river is in our veins”: re-defining river restoration in three Indigenous communities - Coleen A. Fox; Nicholas James Reo; Dale A. Turner; JoAnne Cook; Frank Dituri; Brett Fessell; James Jenkins; Aimee Johnson; Terina M. Rakena; Chris Riley; Ashleigh Turner; Julian Williams; et al. (Sustainability Science, 2017)

Markers of physiological stress during exercise under conditions of normoxia, normobaric hypoxia, hypobaric hypoxia, and genuine high altitude - David Richard Woods; John Paul O’Hara; Christopher John Boos; Peter David Hodkinson; Costas Tsakirides; Neil Edward Hill; Darren Jose; Amanda Hawkins; Kelly Phillipson; Antonia Hazlerigg; Nicola Arjomandkhah; Liam Gallagher; et al. (European Journal of Applied Physiology, 2017)

Den selection by barren-ground grizzly bears, Mackenzie Delta, Northwest Territories - Corey A. Smereka; Mark A. Edwards; Jodie Pongracz; Marsha Branigan; Nicholas W. Pilfold; Andrew E. Derocher (Polar Biology, 2017)

Shocked monazite chronometry: integrating microstructural and in situ isotopic age data for determining precise impact ages - Timmons M. Erickson; Nicholas E. Timms; Christopher L. Kirkland; Eric Tohver; Aaron J. Cavosie; Mark A. Pearce; Steven M. Reddy (Contributions to Mineralogy and Petrology, 2017)

Erratum to: Preliminary characterization of Tasmanian aquareovirus (TSRV) isolates - Sandra C. Zainathan; Jeremy Carson; Mark St. J. Crane; Lynette M. Williams; John Hoad; Nicholas J. G. Moody; Nicholas Gudkovs; Andrew Leis; Sandra Crameri; Alex D. Hyatt; John Young; Barbara F. Nowak (Archives of Virology, 2017)

Preliminary characterization of Tasmanian aquareovirus (TSRV) isolates - Sandra C. Zainathan; Jeremy Carson; Mark St. J. Crane; Lynette M. Williams; John Hoad; Nicholas J. G. Moody; Nicholas Gudkovs; Sandra Crameri; Alex D. Hyatt; John Young; Barbara F. Nowak (Archives of Virology, 2017)

Opsins have evolved under the permanent heterozygote model: insights from phylotranscriptomics of Odonata - Anton Suvorov; Nicholas O. Jensen; Camilla R. Sharkey; M. Stanley Fujimoto; Paul Bodily; Haley M. Cahill Wightman; T. Heath Ogden; Mark J. Clement; Seth M. Bybee (Molecular Ecology, 2017)
Gene duplication plays a central role in adaptation to novel environments by providing new genetic material for functional divergence and evolution of biological complexity. Several evolutionary models have been proposed for gene duplication to explain how new gene copies are preserved by natural selection, but these models have rarely been tested using empirical data. Opsin proteins, when combined with a chromophore, form a photopigment that is responsible for the absorption of light, the first step in the phototransduction cascade. Adaptive gene duplications have occurred many times within the animal opsins’ gene family, leading to novel wavelength sensitivities. Consequently, opsins are an attractive choice for the study of gene duplication evolutionary models. Odonata (dragonflies and damselflies) have the largest opsin repertoire of any insect currently known. Additionally, there is tremendous variation in opsin copy number between species, particularly in the long‐wavelength‐sensitive ( LWS ) class. Using comprehensive phylotranscriptomic and statistical approaches, we tested various evolutionary models of gene duplication. Our results suggest that both the blue‐sensitive ( BS ) and LWS opsin classes were subjected to strong positive selection that greatly weakens after multiple duplication events, a pattern that is consistent with the permanent heterozygote model. Due to the immense interspecific variation and duplicability potential of opsin genes among odonates, they represent a unique model system to test hypotheses regarding opsin gene duplication and diversification at the molecular level.

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

The unseen invaders: introduced earthworms as drivers of change in plant communities in North American forests (a meta‐analysis) - Dylan Craven; Madhav P. Thakur; Erin K. Cameron; Lee E. Frelich; Robin Beauséjour; Robert B. Blair; Bernd Blossey; James Burtis; Amy Choi; Andrea Dávalos; Timothy J. Fahey; Nicholas A. Fisichelli; et al. (Global Change Biology, 2017)
Globally, biological invasions can have strong impacts on biodiversity as well as ecosystem functioning. While less conspicuous than introduced aboveground organisms, introduced belowground organisms may have similarly strong effects. Here, we synthesize for the first time the impacts of introduced earthworms on plant diversity and community composition in North American forests. We conducted a meta‐analysis using a total of 645 observations to quantify mean effect sizes of associations between introduced earthworm communities and plant diversity, cover of plant functional groups, and cover of native and non‐native plants. We found that plant diversity significantly declined with increasing richness of introduced earthworm ecological groups. While plant species richness or evenness did not change with earthworm invasion, our results indicate clear changes in plant community composition: cover of graminoids and non‐native plant species significantly increased, and cover of native plant species (of all functional groups) tended to decrease, with increasing earthworm biomass. Overall, these findings support the hypothesis that introduced earthworms facilitate particular plant species adapted to the abiotic conditions of earthworm‐invaded forests. Further, our study provides evidence that introduced earthworms are associated with declines in plant diversity in North American forests. Changing plant functional composition in these forests may have long‐lasting effects on ecosystem functioning.

Estimates of local biodiversity change over time stand up to scrutiny - Mark Vellend; Maria Dornelas; Lander Baeten; Robin Beauséjour; Carissa D. Brown; Pieter De Frenne; Sarah C. Elmendorf; Nicholas J. Gotelli; Faye Moyes; Isla H. Myers‐Smith; Anne E. Magurran; Brian J. McGill; et al. (Ecology, 2017)
We present new data and analyses revealing fundamental flaws in a critique of two recent meta‐analyses of local‐scale temporal biodiversity change. First, the conclusion that short‐term time series lead to biased estimates of long‐term change was based on two errors in the simulations used to support it. Second, the conclusion of negative relationships between temporal biodiversity change and study duration was entirely dependent on unrealistic model assumptions, the use of a subset of data, and inclusion of one outlier data point in one study. Third, the finding of a decline in local biodiversity, after eliminating post‐disturbance studies, is not robust to alternative analyses on the original data set, and is absent in a larger, updated data set. Finally, the undebatable point, noted in both original papers, that studies in the ecological literature are geographically biased, was used to cast doubt on the conclusion that, outside of areas converted to croplands or asphalt, the distribution of biodiversity trends is centered approximately on zero. Future studies may modify conclusions, but at present, alternative conclusions based on the geographic‐bias argument rely on speculation. In sum, the critique raises points of uncertainty typical of all ecological studies, but does not provide an evidence‐based alternative interpretation.

Microstructural constraints on the mechanisms of the transformation to reidite in naturally shocked zircon - Timmons M. Erickson; Mark A. Pearce; Steven M. Reddy; Nicholas E. Timms; Aaron J. Cavosie; Julien Bourdet; William D. A. Rickard; Alexander A. Nemchin (Contributions to Mineralogy and Petrology, 2017)

Inferring contemporary and historical genetic connectivity from juveniles - Pierre Feutry; Oliver Berry; Peter M. Kyne; Richard D. Pillans; Richard M. Hillary; Peter M. Grewe; James R. Marthick; Grant Johnson; Rasanthi M. Gunasekera; Nicholas J. Bax; Mark Bravington (Molecular Ecology, 2017)
Measuring population connectivity is a critical task in conservation biology. While genetic markers can provide reliable long‐term historical estimates of population connectivity, scientists are still limited in their ability to determine contemporary patterns of gene flow, the most practical time frame for management. Here, we tackled this issue by developing a new approach that only requires juvenile sampling at a single time period. To demonstrate the usefulness of our method, we used the Speartooth shark ( Glyphis glyphis ), a critically endangered species of river shark found only in tropical northern Australia and southern Papua New Guinea. Contemporary adult and juvenile shark movements, estimated with the spatial distribution of kin pairs across and within three river systems, was contrasted with historical long‐term connectivity patterns, estimated from mitogenomes and genome‐wide SNP data. We found strong support for river fidelity in juveniles with the within‐cohort relationship analysis. Male breeding movements were highlighted with the cross‐cohort relationship analysis, and female reproductive philopatry to the river systems was revealed by the mitogenomic analysis. We show that accounting for juvenile river fidelity and female philopatry is important in population structure analysis and that targeted sampling in nurseries and juvenile aggregations should be included in the genomic toolbox of threatened species management.

Comprehensive analysis of nanodiamond evidence relating to the Younger Dryas Impact Hypothesis - Tyrone L. Daulton; Sachiko Amari; Andrew C. Scott; Mark Hardiman; Nicholas Pinter; R. Scott Anderson (Journal of Quaternary Science, 2017)
During the end of the last glacial period in the Northern Hemisphere near 12.9k cal a BP, deglacial warming of the Bølling–Ållerod interstadial ceased abruptly and the climate returned to glacial conditions for an interval of about 1300 years known as the Younger Dryas stadial. The Younger Dryas Impact Hypothesis proposes that the onset of the Younger Dryas climate reversal, Pleistocene megafaunal extinctions and disappearance of the Clovis paleoindian lithic technology were coeval and caused by continent‐wide catastrophic effects of impact/bolide events in North America. While there are no known impact structures dated to the Younger Dryas onset, physical evidence of the impact/bolide events is argued to be present in sediments spanning several continents at stratigraphic levels inferred to date to the Bølling‐Ållerod/Younger Dryas boundary (YDB). Reports of nanometer to submicron‐sized diamonds in YDB sediments, in particular the rare 2H hexagonal polytype of diamond, lonsdaleite, have been presented as strong evidence for shock processing of crustal materials. We review the available data on diamonds in sediments and provide new data. We find no evidence for lonsdaleite in YDB sediments and find no evidence of a spike in nanodiamond concentration at the YDB layer to support the impact hypothesis.

Interpreting palaeofire evidence from fluvial sediments: a case study from Santa Rosa Island, California, with implications for the Younger Dryas Impact Hypothesis - Andrew C. Scott; Mark Hardiman; Nicholas Pinter; R. Scott Anderson; Tyrone L. Daulton; Ana Ejarque; Paul Finch; Alice Carter‐champion (Journal of Quaternary Science, 2017)
Fluvial sequences from the late Pleistocene to the Holocene are exposed in Arlington Canyon, Santa Rosa Island, Northern Channel Islands, California, USA, including one outcrop that features centrally in the controversial hypothesis of an extra‐terrestrial impact at the onset of the Younger Dryas. The fluvial sequence in Arlington Canyon contains a significant quantity and range of organic material, much of which has been charred. The purpose of this study was to systematically describe the key outcrop of the Arlington sequence, provide new radiocarbon age control and analyse organic material in the Arlington sediments within a rigorous palaeobotanical and palaeo‐charcoal context. These analyses provide a test of previous claims for catastrophic impact‐induced fire in Arlington Canyon. Carbonaceous spherular materials were identified as predominantly fungal sclerotia; ‘carbon elongates’ are predominantly arthropod coprolites, including termite frass. ‘Glassy carbon’ formed from the precipitation of tars during charcoalification. None of these materials indicate high‐temperature formation or combustion. Charcoal and other materials in Arlington Canyon document widespread and frequent fires both before and after the onset of the Younger Dryas, recording predominantly low‐temperature surface fires. In summary, we find no evidence in Arlington Canyon for an extra‐terrestrial impact or catastrophic impact‐induced fire.

Emerging Opportunities for Landscape Ecological Modelling - Nicholas W. Synes; Calum Brown; Kevin Watts; Steven M. White; Mark A. Gilbert; Justin M. J. Travis (Current Landscape Ecology Reports, 2016)

Hierarchical filters determine community assembly of urban species pools - Myla F. J. Aronson; Charles H. Nilon; Christopher A. Lepczyk; Tommy S. Parker; Paige S. Warren; Sarel S. Cilliers; Mark A. Goddard; Amy K. Hahs; Cecilia Herzog; Madhusudan Katti; Frank A. La Sorte; Nicholas S. G. Williams; et al. (Ecology, 2016)
The majority of humanity now lives in cities or towns, with this proportion expected to continue increasing for the foreseeable future. As novel ecosystems, urban areas offer an ideal opportunity to examine multi‐scalar processes involved in community assembly as well as the role of human activities in modulating environmental drivers of biodiversity. Although ecologists have made great strides in recent decades at documenting ecological relationships in urban areas, much remains unknown, and we still need to identify the major ecological factors, aside from habitat loss, behind the persistence or extinction of species and guilds of species in cities. Given this paucity of knowledge, there is an immediate need to facilitate collaborative, interdisciplinary research on the patterns and drivers of biodiversity in cities at multiple spatial scales. In this review, we introduce a new conceptual framework for understanding the filtering processes that mold diversity of urban floras and faunas. We hypothesize that the following hierarchical series of filters influence species distributions in cities: (1) regional climatic and biogeographical factors; (2) human facilitation; (3) urban form and development history; (4) socioeconomic and cultural factors; and (5) species interactions. In addition to these filters, life history and functional traits of species are important in determining community assembly and act at multiple spatial scales. Using these filters as a conceptual framework can help frame future research needed to elucidate processes of community assembly in urban areas. Understanding how humans influence community structure and processes will aid in the management, design, and planning of our cities to best support biodiversity.

Transmission of influenza reflects seasonality of wild birds across the annual cycle - Nichola J. Hill; Eric J. Ma; Brandt W. Meixell; Mark S. Lindberg; Walter M. Boyce; Jonathan A. Runstadler (Ecology Letters, 2016)
Influenza A Viruses (IAV) in nature must overcome shifting transmission barriers caused by the mobility of their primary host, migratory wild birds, that change throughout the annual cycle. Using a phylogenetic network of viral sequences from North American wild birds (2008–2011) we demonstrate a shift from intraspecific to interspecific transmission that along with reassortment, allows IAV to achieve viral flow across successive seasons from summer to winter. Our study supports amplification of IAV during summer breeding seeded by overwintering virus persisting locally and virus introduced from a wide range of latitudes. As birds migrate from breeding sites to lower latitudes, they become involved in transmission networks with greater connectivity to other bird species, with interspecies transmission of reassortant viruses peaking during the winter. We propose that switching transmission dynamics may be a critical strategy for pathogens that infect mobile hosts inhabiting regions with strong seasonality.

Testosterone enables growth and hypertrophy in fusion impaired myoblasts that display myotube atrophy: deciphering the role of androgen and IGF-I receptors - David C. Hughes; Claire E. Stewart; Nicholas Sculthorpe; Hannah F. Dugdale; Farzad Yousefian; Mark P. Lewis; Adam P. Sharples (Biogerontology, 2016)

Farmland biodiversity and agricultural management on 237 farms in 13 European and two African regions - Gisela Lüscher; Youssef Ammari; Aljona Andriets; Siyka Angelova; Michaela Arndorfer; Debra Bailey; Katalin Balázs; Marion Bogers; Robert G. H. Bunce; Jean‐Philippe Choisis; Peter Dennis; Mario Díaz; et al. (Ecology, 2016)
Farmland is a major land cover type in Europe and Africa and provides habitat for numerous species. The severe decline in farmland biodiversity of the last decades has been attributed to changes in farming practices, and organic and low‐input farming are assumed to mitigate detrimental effects of agricultural intensification on biodiversity. Since the farm enterprise is the primary unit of agricultural decision making, management‐related effects at the field scale need to be assessed at the farm level. Therefore, in this study, data were collected on habitat characteristics, vascular plant, earthworm, spider, and bee communities and on the corresponding agricultural management in 237 farms in 13 European and two African regions. In 15 environmental and agricultural homogeneous regions, 6–20 farms with the same farm type (e.g., arable crops, grassland, or specific permanent crops) were selected. If available, an equal number of organic and non‐organic farms were randomly selected. Alternatively, farms were sampled along a gradient of management intensity. For all selected farms, the entire farmed area was mapped, which resulted in total in the mapping of 11 338 units attributed to 194 standardized habitat types, provided together with additional descriptors. On each farm, one site per available habitat type was randomly selected for species diversity investigations. Species were sampled on 2115 sites and identified to the species level by expert taxonomists. Species lists and abundance estimates are provided for each site and sampling date (one date for plants and earthworms, three dates for spiders and bees). In addition, farmers provided information about their management practices in face‐to‐face interviews following a standardized questionnaire. Farm management indicators for each farm are available (e.g., nitrogen input, pesticide applications, or energy input). Analyses revealed a positive effect of unproductive areas and a negative effect of intensive management on biodiversity. Communities of the four taxonomic groups strongly differed in their response to habitat characteristics, agricultural management, and regional circumstances. The data has potential for further insights into interactions of farmland biodiversity and agricultural management at site, farm, and regional scale.

Vascular plants promote ancient peatland carbon loss with climate warming - Tom N. Walker; Mark H. Garnett; Susan E. Ward; Simon Oakley; Richard D. Bardgett; Nicholas J. Ostle (Global Change Biology, 2016)
Northern peatlands have accumulated one third of the Earth's soil carbon stock since the last Ice Age. Rapid warming across northern biomes threatens to accelerate rates of peatland ecosystem respiration. Despite compensatory increases in net primary production, greater ecosystem respiration could signal the release of ancient, century‐ to millennia‐old carbon from the peatland organic matter stock. Warming has already been shown to promote ancient peatland carbon release, but, despite the key role of vegetation in carbon dynamics, little is known about how plants influence the source of peatland ecosystem respiration. Here, we address this issue using in situ 14 C measurements of ecosystem respiration on an established peatland warming and vegetation manipulation experiment. Results show that warming of approximately 1 °C promotes respiration of ancient peatland carbon (up to 2100 years old) when dwarf‐shrubs or graminoids are present, an effect not observed when only bryophytes are present. We demonstrate that warming likely promotes ancient peatland carbon release via its control over organic inputs from vascular plants. Our findings suggest that dwarf‐shrubs and graminoids prime microbial decomposition of previously ‘locked‐up’ organic matter from potentially deep in the peat profile, facilitating liberation of ancient carbon as CO 2 . Furthermore, such plant‐induced peat respiration could contribute up to 40% of ecosystem CO 2 emissions. If consistent across other subarctic and arctic ecosystems, this represents a considerable fraction of ecosystem respiration that is currently not acknowledged by global carbon cycle models. Ultimately, greater contribution of ancient carbon to ecosystem respiration may signal the loss of a previously stable peatland carbon pool, creating potential feedbacks to future climate change.

S almonella infection in grey seals ( H alichoerus grypus ), a marine mammal sentinel species: pathogenicity and molecular typing of S almonella strains compared with human and livestock isolates - Johanna L. Baily; Geoffrey Foster; Derek Brown; Nicholas J. Davison; John E. Coia; Eleanor Watson; Romain Pizzi; Kim Willoughby; Ailsa J. Hall; Mark P. Dagleish (Environmental Microbiology, 2016)
Summary Microbial pollution of the marine environment through land–sea transfer of human and livestock pathogens is of concern. S almonella was isolated from rectal swabs of free‐ranging and stranded grey seal pups (21.1%; 37/175) and compared with strains from the same serovars isolated from human clinical cases, livestock, wild mammals and birds in Scotland, UK to characterize possible transmission routes using pulsed‐field gel electrophoresis and multi‐locus variable number of tandem repeat analyses. A higher prevalence of S almonella was found in pups exposed to seawater, suggesting that this may represent a source of this pathogen. S almonella Bovismorbificans was the most common isolate (18.3% pups; 32/175) and was indistinguishable from isolates found in Scottish cattle. S almonella T yphimurium was infrequent (2.3% pups; 4/175), mostly similar to isolates found in garden birds and, in one case, identical to a highly multidrug resistant strain isolated from a human child. S almonella H aifa was rare (1.1% pups; 2/175), but isolates were indistinguishable from that of a human clinical isolate. These results suggest that S . Bovismorbificans may circulate between grey seal and cattle populations and that both S . Typhimurium and S . Haifa isolates are shared with humans, raising concerns of microbial marine pollution.

Meta-studies in land use science: Current coverage and prospects - Jasper van Vliet; Nicholas R. Magliocca; Bianka Büchner; Elizabeth Cook; José M. Rey Benayas; Erle C. Ellis; Andreas Heinimann; Eric Keys; Tien Ming Lee; Jianguo Liu; Ole Mertz; Patrick Meyfroidt; et al. (Ambio, 2016)

Germline TERT promoter mutations are rare in familial melanoma - Mark Harland; Mia Petljak; Carla Daniela Robles-Espinoza; Zhihao Ding; Nelleke A. Gruis; Remco van Doorn; Karen A. Pooley; Alison M. Dunning; Lauren G. Aoude; Karin A. W. Wadt; Anne-Marie Gerdes; Kevin M. Brown; et al. (Familial Cancer, 2016)

Distraction produces over-additive increases in the degree to which alcohol impairs driving performance - Nicholas A. Van Dyke; Mark T. Fillmore (Psychopharmacology, 2015)

Posteromedial hyperactivation during episodic recognition among people with memory decline: findings from the WRAP study - Christopher R. Nicholas; Ozioma C. Okonkwo; Barbara B. Bendlin; Jennifer M. Oh; Sanjay Asthana; Howard A. Rowley; Bruce Hermann; Mark A. Sager; Sterling C. Johnson (Brain Imaging and Behavior, 2015)

Structural Characterisation of Non-Deamidated Acidic Variants of Erwinia chrysanthemi L-asparaginase Using Small-Angle X-ray Scattering and Ion-Mobility Mass Spectrometry - David Gervais; Darryl King; Patrick Kanda; Nicholas Foote; Lucy Elliott; Phillip Brown; Natacha O. Lee; Konstantinos Thalassinos; Claire Pizzey; Robert Rambo; Thomas C. Minshull; Mark J. Dickman; et al. (Pharmaceutical Research, 2015)

Citizen science contributes to our knowledge of invasive plant species distributions - Alycia W. Crall; Catherine S. Jarnevich; Nicholas E. Young; Brendon J. Panke; Mark Renz; Thomas J. Stohlgren (Biological Invasions, 2015)

Atmospheric particulate matter in proximity to mountaintop coal mines: sources and potential environmental and human health impacts - Laura Kurth; Allan Kolker; Mark Engle; Nicholas Geboy; Michael Hendryx; William Orem; Michael McCawley; Lynn Crosby; Calin Tatu; Matthew Varonka; Christina DeVera (Environmental Geochemistry and Health, 2015)

Learning to Associate Auditory and Visual Stimuli: Behavioral and Neural Mechanisms - Nicholas Altieri; Ryan A. Stevenson; Mark T. Wallace; Michael J. Wenger (Brain Topography, 2015)

The promise and peril of intensive‐site‐based ecological research: insights from the Hubbard Brook ecosystem study - Timothy J. Fahey; Pamela H. Templer; Bruce T. Anderson; John J. Battles; John L. Campbell; Charles T. Driscoll; Anthony R. Fusco; Mark B. Green; Karim-Aly S. Kassam; Nicholas L. Rodenhouse; Lindsey Rustad; Paul G. Schaberg; et al. (Ecology, 2015)
Ecological research is increasingly concentrated at particular locations or sites. This trend reflects a variety of advantages of intensive, site‐based research, but also raises important questions about the nature of such spatially delimited research: how well does site based research represent broader areas, and does it constrain scientific discovery? We provide an overview of these issues with a particular focus on one prominent intensive research site: the Hubbard Brook Experimental Forest (HBEF), New Hampshire, USA. Among the key features of intensive sites are: long‐term, archived data sets that provide a context for new discoveries and the elucidation of ecological mechanisms; the capacity to constrain inputs and parameters, and to validate models of complex ecological processes; and the intellectual cross‐fertilization among disciplines in ecological and environmental sciences. The feasibility of scaling up ecological observations from intensive sites depends upon both the phenomenon of interest and the characteristics of the site. An evaluation of deviation metrics for the HBEF illustrates that, in some respects, including sensitivity and recovery of streams and trees from acid deposition, this site is representative of the Northern Forest region, of which HBEF is a part. However, the mountainous terrain and lack of significant agricultural legacy make the HBEF among the least disturbed sites in the Northern Forest region. Its relatively cool, wet climate contributes to high stream flow compared to other sites. These similarities and differences between the HBEF and the region can profoundly influence ecological patterns and processes and potentially limit the generality of observations at this and other intensive sites. Indeed, the difficulty of scaling up may be greatest for ecological phenomena that are sensitive to historical disturbance and that exhibit the greatest spatiotemporal variation, such as denitrification in soils and the dynamics of bird communities. Our research shows that end member sites for some processes often provide important insights into the behavior of inherently heterogeneous ecological processes. In the current era of rapid environmental and biological change, key ecological responses at intensive sites will reflect both specific local drivers and regional trends.

Does flood rhythm drive ecosystem responses in tropical riverscapes? - Timothy D. Jardine; Nicholas R. Bond; Michele A. Burford; Mark J. Kennard; Douglas P. Ward; Peter Bayliss; Peter M. Davies; Michael M. Douglas; Stephen K. Hamilton; John M. Melack; Robert J. Naiman; Neil E. Pettit; et al. (Ecology, 2015)
Biotic communities are shaped by adaptations from generations of exposure to selective pressures by recurrent and often infrequent events. In large rivers, floods can act as significant agents of change, causing considerable physical and biotic disturbance while often enhancing productivity and diversity. We show that the relative balance between these seemingly divergent outcomes can be explained by the rhythmicity, or predictability of the timing and magnitude, of flood events. By analyzing biological data for large rivers that span a gradient of rhythmicity in the Neotropics and tropical Australia, we find that systems with rhythmic annual floods have higher fish species richness, more stable avian populations, and elevated rates of riparian forest production compared with those with arrhythmic flood pulses. Intensification of the hydrological cycle driven by climate change, coupled with reductions in runoff due to water extractions for human use and altered discharge from impoundments, is expected to alter the hydrologic rhythmicity of floodplain rivers with significant consequences for both biodiversity and productivity.

Taking animal tracking to new depths: synthesizing horizontal–vertical movement relationships for four marine predators - Sophie Bestley; Ian D. Jonsen; Mark A. Hindell; Robert G. Harcourt; Nicholas J. Gales (Ecology, 2015)
In animal ecology, a question of key interest for aquatic species is how changes in movement behavior are related in the horizontal and vertical dimensions when individuals forage. Alternative theoretical models and inconsistent empirical findings mean that this question remains unresolved. Here we tested expectations by incorporating the vertical dimension (dive information) when predicting switching between movement states (“resident” or “directed”) within a state‐space model. We integrated telemetry‐based tracking and diving data available for four seal species (southern elephant, Weddell, antarctic fur, and crabeater) in East Antarctica. Where possible, we included dive variables derived from the relationships between (1) dive duration and depth (as a measure of effort), and (2) dive duration and the postdive surface interval (as a physiological measure of cost). Our results varied within and across species, but there was a general tendency for the probability of switching into “resident” state to be positively associated with shorter dive durations (for a given depth) and longer postdive surface intervals (for a given dive duration). Our results add to a growing body of literature suggesting that simplistic interpretations of optimal foraging theory based only on horizontal movements do not directly translate into the vertical dimension in dynamic marine environments. Analyses that incorporate at least two dimensions can test more sophisticated models of foraging behavior.

Operationalizing resilience for adaptive coral reef management under global environmental change - Kenneth R.N. Anthony; Paul A. Marshall; Ameer Abdulla; Roger Beeden; Chris Bergh; Ryan Black; C. Mark Eakin; Edward T. Game; Margaret Gooch; Nicholas A.J. Graham; Alison Green; Scott F. Heron; et al. (Global Change Biology, 2015)
Cumulative pressures from global climate and ocean change combined with multiple regional and local‐scale stressors pose fundamental challenges to coral reef managers worldwide. Understanding how cumulative stressors affect coral reef vulnerability is critical for successful reef conservation now and in the future. In this review, we present the case that strategically managing for increased ecological resilience (capacity for stress resistance and recovery) can reduce coral reef vulnerability (risk of net decline) up to a point. Specifically, we propose an operational framework for identifying effective management levers to enhance resilience and support management decisions that reduce reef vulnerability. Building on a system understanding of biological and ecological processes that drive resilience of coral reefs in different environmental and socio‐economic settings, we present an Adaptive Resilience‐Based management ( ARBM ) framework and suggest a set of guidelines for how and where resilience can be enhanced via management interventions. We argue that press‐type stressors (pollution, sedimentation, overfishing, ocean warming and acidification) are key threats to coral reef resilience by affecting processes underpinning resistance and recovery, while pulse‐type (acute) stressors (e.g. storms, bleaching events, crown‐of‐thorns starfish outbreaks) increase the demand for resilience. We apply the framework to a set of example problems for Caribbean and Indo‐Pacific reefs. A combined strategy of active risk reduction and resilience support is needed, informed by key management objectives, knowledge of reef ecosystem processes and consideration of environmental and social drivers. As climate change and ocean acidification erode the resilience and increase the vulnerability of coral reefs globally, successful adaptive management of coral reefs will become increasingly difficult. Given limited resources, on‐the‐ground solutions are likely to focus increasingly on actions that support resilience at finer spatial scales, and that are tightly linked to ecosystem goods and services.

Identifying and Quantifying Multisensory Integration: A Tutorial Review - Ryan A. Stevenson; Dipanwita Ghose; Juliane Krueger Fister; Diana K. Sarko; Nicholas A. Altieri; Aaron R. Nidiffer; LeAnne R. Kurela; Justin K. Siemann; Thomas W. James; Mark T. Wallace (Brain Topography, 2014)

Three-way compositional analysis of water quality monitoring data - Mark A. Engle; Michele Gallo; Karl T. Schroeder; Nicholas J. Geboy; John W. Zupancic (Environmental and Ecological Statistics, 2014)

Validation of PyMBMS as a High-throughput Screen for Lignin Abundance in Lignocellulosic Biomass of Grasses - Bryan W. Penning; Robert W. Sykes; Nicholas C. Babcock; Christopher K. Dugard; John F. Klimek; David Gamblin; Mark Davis; Timothy R. Filley; Nathan S. Mosier; Clifford F. Weil; Maureen C. McCann; Nicholas C. Carpita (BioEnergy Research, 2014)

You are what you eat: fatty acid profiles as a method to track the habitat movement of an insect - Stephen K. Bayes; Marc K. Hellerstein; Mark Fitch; Nicholas J. Mills; Stephen C. Welter (Oecologia, 2014)

Assessing coastal species distribution models through the integration of terrestrial, oceanic and atmospheric data - Gregory J. M. Rickbeil; Nicholas C. Coops; Mark C. Drever; Trisalyn A. Nelson (Journal of Biogeography, 2014)
Aim When considering multiple species in distribution models, environmental variables should be selected that describe the group of species' environmental requirements. This can, however, be challenging in locations such as coastal areas, where different species may respond to terrestrial, oceanic and/or atmospheric conditions. Here, we evaluate the use of remotely sensed ( RS ) terrestrial, oceanic and interpolated climate variables, as well as a more detailed shore‐zone data set, as a means of modelling the distributions of coastal bird species with diverse habitat requirements. Location Coastal British Columbia, Canada. Methods Boosted regression trees were used to model the distributions of 60 species of coastal birds using each environmental variable group, run individually and in combination. Models were assessed for their predictive ability and model fit, as well as for model overfitting. Results Models that incorporated terrestrial data were found to produce the highest model fit and predictive ability of the broad‐scale environmental groups. Incorporating the fine‐scale shore‐zone data offered little improvement, as did selecting the best model in terms of predictive ability by species. Model fit and predictive ability were also found to vary by functional feeding group, with insectivores and benthivores being the best‐modelled. Main conclusions Having access to both broad‐scale RS environmental data and more detailed coastal shore‐zone data produced modest improvements over employing RS environmental data alone. Models using only the terrestrial data set, however, performed similarly to the best single model type (terrestrial + shore‐zone), indicating that broad‐scale environmental data also offer an effective means of estimating coastal bird distributions. Testing multiple environmental variable groups in different combinations and selecting the best model allowed models to be optimized by species; conversely, the results of a ‘one model fits all’ approach were comparable to those of the best models, indicating that a single‐model approach is also valid.

Long-term behavior at foraging sites of adult female loggerhead sea turtles (Caretta caretta) from three Florida rookeries - Allen M. Foley; Barbara A. Schroeder; Robert Hardy; Sandra L. MacPherson; Mark Nicholas (Marine Biology, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

H alomonas sulfidaeris ‐dominated microbial community inhabits a 1.8 km‐deep subsurface C ambrian S andstone reservoir - Yiran Dong; Charu Gupta Kumar; Nicholas Chia; Pan‐Jun Kim; Philip A. Miller; Nathan D. Price; Isaac K. O. Cann; Theodore M. Flynn; Robert A. Sanford; Ivan G. Krapac; Randall A. Locke; Pei‐Ying Hong; et al. (Environmental Microbiology, 2014)
Summary A low‐diversity microbial community, dominated by the γ ‐proteobacterium H alomonas sulfidaeris , was detected in samples of warm saline formation porewater collected from the C ambrian Mt. S imon S andstone in the I llinois B asin of the N orth A merican M idcontinent (1.8 km/5872 ft burial depth, 50° C , pH 8, 181 bars pressure). These highly porous and permeable quartz arenite sandstones are directly analogous to reservoirs around the world targeted for large‐scale hydrocarbon extraction, as well as subsurface gas and carbon storage. A new downhole low‐contamination subsurface sampling probe was used to collect in situ formation water samples for microbial environmental metagenomic analyses. Multiple lines of evidence suggest that this H . sulfidaeris ‐dominated subsurface microbial community is indigenous and not derived from drilling mud microbial contamination. Data to support this includes V 1‐ V 3 pyrosequencing of formation water and drilling mud, as well as comparison with previously published microbial analyses of drilling muds in other sites. Metabolic pathway reconstruction, constrained by the geology, geochemistry and present‐day environmental conditions of the Mt . S imon S andstone, implies that H . sulfidaeris ‐dominated subsurface microbial community may utilize iron and nitrogen metabolisms and extensively recycle indigenous nutrients and substrates. The presence of aromatic compound metabolic pathways suggests this microbial community can readily adapt to and survive subsurface hydrocarbon migration.

Mechanisms of drift-feeding behavior in juvenile Chinook salmon and the role of inedible debris in a clear-water Alaskan stream - Jason Neuswanger; Mark S. Wipfli; Amanda E. Rosenberger; Nicholas F. Hughes (Environmental Biology of Fishes, 2014)

Differentiation between sediment and hypolimnion methanogen communities in humic lakes - Nicholas D. Youngblut; Mark Dell'Aringa; Rachel J. Whitaker (Environmental Microbiology, 2014)
Summary The traditional view of carbon cycling within the pelagic zone of freshwater lakes has consisted of methane production within the anoxic sediment, followed by diffusive flux and ebullition through the water column. Methanogenic archaea have been shown to be present within the water columns of freshwater lakes; however, little is known about whether these methanogenic communities are distinct from those in the sediment or how these communities change over space and time. We used the methanogen‐specific phylogenetic marker mcrA to perform a 3‐year study focusing on the community structure of methanogens within the sediment and anoxic hypolimnion water layer of five humic lakes in WI , USA . The hypolimnion and sediment communities were distinct in composition, richness and phylogenetic diversity. Hypolimnion communities displayed a temporally stable biogeographical pattern among lakes, which was driven by both lake‐specific environmental variables and barriers to dispersal. We conclude that the hypolimnion comprised communities of methanogens that are distinct from those in the sediment, differentiated among lakes, and likely have unique ecological roles and evolutionary trajectories in these anaerobic environments.

Appropriate Uses and Practical Limitations of 2D Numerical Analysis of Tunnels and Tunnel Support Response - Nicholas Vlachopoulos; Mark S. Diederichs (Geotechnical and Geological Engineering, 2014)

The effect of urban ground covers on arthropods: An experiment - Briony A. Norton; Linda J. Thomson; Nicholas S. G. Williams; Mark J. McDonnell (Urban Ecosystems, 2014)

Human stick balancing: an intermittent control explanation - Peter Gawthrop; Kwee-Yum Lee; Mark Halaki; Nicholas O’Dwyer (Biological Cybernetics, 2013)

Reaction mechanism for the replacement of calcite by dolomite and siderite: implications for geochemistry, microstructure and porosity evolution during hydrothermal mineralisation - Mark A. Pearce; Nicholas E. Timms; Robert M. Hough; James S. Cleverley (Contributions to Mineralogy and Petrology, 2013)

GidA Expression in Salmonella is Modulated Under Certain Environmental Conditions - Jaclyn M. Rehl; Daniel C. Shippy; Nicholas M. Eakley; Megan D. Brevik; Jordan M. Sand; Mark E. Cook; Amin A. Fadl (Current Microbiology, 2013)

Feedbacks underlie the resilience of salt marshes and rapid reversal of consumer‐driven die‐off - Andrew H. Altieri; Mark D. Bertness; Tyler C. Coverdale; Eric E. Axelman; Nicholas C. Herrmann; P. Lauren Szathmary (Ecology, 2013)
Understanding ecosystem resilience to human impacts is critical for conservation and restoration. The large‐scale die‐off of New England salt marshes was triggered by overfishing and resulted from decades of runaway crab grazing. In 2009, however, cordgrass began to recover, decreasing die‐off ∼40% by 2010. We used surveys and experiments to test whether plant–substrate feedbacks underlie marsh resilience. Initially, grazer‐generated die‐off swept through the cordgrass, creating exposed, stressful peat banks that inhibited plant growth. This desertification cycle broke when banks eroded and peat transitioned into mud with fewer herbivores, less grazing, and lower physical stress. Cordgrass reestablished in these areas through a feedback where it engineered a recovery zone by further ameliorating physical stresses and facilitating additional revegetation. Our results reveal that feedbacks can play a critical role in rapid, reversible ecosystem shifts associated with human impacts, and that the interplay of facilitative and consumer interactions should be incorporated into resilience theory.

Areas of high diversity for the world’s inland-breeding waterbirds - Laura Williamson; Michael Hudson; Mark O’Connell; Nicholas Davidson; Richard Young; Tatsuya Amano; Tamás Székely (Biodiversity and Conservation, 2013)

HVP10 encoding V-PPase is a prime candidate for the barley HvNax3 sodium exclusion gene: evidence from fine mapping and expression analysis - Yuri Shavrukov; Jessica Bovill; Irfan Afzal; Julie E. Hayes; Stuart J. Roy; Mark Tester; Nicholas C. Collins (Planta, 2013)

Enhancement of social novelty discrimination by positive allosteric modulators at metabotropic glutamate 5 receptors: adolescent administration prevents adult-onset deficits induced by neonatal treatment with phencyclidine - Nicholas E. Clifton; Nadège Morisot; Sylvie Girardon; Mark J. Millan; Florence Loiseau (Psychopharmacology, 2013)

Relationships between ecosystem metabolism, benthic macroinvertebrate densities, and environmental variables in a sub-arctic Alaskan river - Emily R. Benson; Mark S. Wipfli; Joanne E. Clapcott; Nicholas F. Hughes (Hydrobiologia, 2013)

Genome-wide study identifies two loci associated with lung function decline in mild to moderate COPD - Nadia N. Hansel; Ingo Ruczinski; Nicholas Rafaels; Don D. Sin; Denise Daley; Alla Malinina; Lili Huang; Andrew Sandford; Tanda Murray; Yoonhee Kim; Candelaria Vergara; Susan R. Heckbert; et al. (Human Genetics, 2013)

Plant pest and disease diagnosis using electronic nose and support vector machine approach - Reza Ghaffari; Jullada Laothawornkitkul; Daciana Iliescu; Evor Hines; Mark Leeson; Richard Napier; Jason P Moore; Nigel D Paul; C Nicholas Hewitt; Jane E Taylor (Journal of Plant Diseases and Protection, 2012)

A new paradigm for human stick balancing: a suspended not an inverted pendulum - Kwee-Yum Lee; Nicholas O’Dwyer; Mark Halaki; Richard Smith (Experimental Brain Research, 2012)

A trophic cascade triggers collapse of a salt‐marsh ecosystem with intensive recreational fishing - Andrew H. Altieri; Mark D. Bertness; Tyler C. Coverdale; Nicholas C. Herrmann; Christine Angelini (Ecology, 2012)
Overexploitation of predators has been linked to the collapse of a growing number of shallow‐water marine ecosystems. However, salt‐marsh ecosystems are often viewed and managed as systems controlled by physical processes, despite recent evidence for herbivore‐driven die‐off of marsh vegetation. Here we use field observations, experiments, and historical records at 14 sites to examine whether the recently reported die‐off of northwestern Atlantic salt marshes is associated with the cascading effects of predator dynamics and intensive recreational fishing activity. We found that the localized depletion of top predators at sites accessible to recreational anglers has triggered the proliferation of herbivorous crabs, which in turn results in runaway consumption of marsh vegetation. This suggests that overfishing may be a general mechanism underlying the consumer‐driven die‐off of salt marshes spreading throughout the western Atlantic. Our findings support the emerging realization that consumers play a dominant role in regulating marine plant communities and can lead to ecosystem collapse when their impacts are amplified by human activities, including recreational fishing.

Silviculture and Forest Ecology - David Mercker; Ryan Blair; Don Tyler; Theresa Jain; Russell Graham; Donald Rockwood; Nicholas Koch; Jeremy Brawner; Omar Carrero; Kristofer Covey; Alex Barrett; Mark Ashton; et al. (Journal of Forestry, 2011)
2Over the past several decades, federal incentive programs have encouraged the restoration of bottomland forests throughout the West Gulf Coastal Plain (WGCP) and the Lower Mississippi Alluvial Valley (LMAV). Programs such as the Conservation Reserve (CRP) and Wetlands Reserve (WRP) Programs have been marginally successful (Stanturf et al. 2001). Foresters and contractors often follow conventional tree planting procedures that are well established for upland sites, but prove problematic in bottomlands. High water tables, soil drainage and compaction, overland flooding and diverse soil properties make species selection difficult. Slight changes in topography and soil structure often have a dramatic effect on survival and growth of planted oak seedlings (Hodges and Schweitzer 1979). This project documented the survival and growth of six-year old seedlings that were established on a bottomland site in 2004, located at the West Tennessee Research and Education Center, Jackson, Tennessee. The purpose was to determine how soil drainage as indicated by mottling (specifically, the point of 50 percent gray color throughout the soil profile) affects the survival and growth of bottomland oak species. The findings suggest that practitioners plant Nuttall, pin and overcup oaks in poorly drained soils. As the drainage improves, begin mixing in willow oak. In the best drained soils (if they exist), finish by including water, swamp chestnut, swamp white, Shumard, cherrybark and bur oaks. Potential species diversity should expand as the soil drainage improves.

Cytonuclear evidence for hybridogenetic reproduction in natural populations of the Australian carp gudgeon ( Hypseleotris : Eleotridae) - DANIEL J. SCHMIDT; NICHOLAS R. BOND; MARK ADAMS; JANE M. HUGHES (Molecular Ecology, 2011)
Although most vertebrates reproduce sexually, a small number of fishes, amphibians and reptiles are known in which reproduction is asexual, i.e. without meiotic recombination. In fishes, these so‐called unisexual lineages usually comprise only females and utilize co‐occurring males of a related sexual species to reproduce via gynogenesis or hybridogenesis. Here, we examine patterns of microsatellite and mitochondrial DNA (mtDNA) variation in a widespread group of freshwater fishes (carp gudgeons; Hypseleotris spp.) to investigate a long‐standing proposal that this group includes unisexual forms. We show that the mtDNA genome of most carp gudgeons in tributaries of the Goulburn River belongs to one of two deeply divided clades (∼10% cyt b divergence) and that nuclear variation divides the same individuals into four distinct groups. Group 1 exhibits the genotypic proportions of a random mating population and has a 1:1 sex ratio. Two other groups are extremely sex‐biased (98% male, 96% female), exhibit excess heterozygosity at most loci and share at least one allele per locus with group 1. We propose that these two groups represent ‘unisexual’ hybridogenetic lineages and that both utilize co‐occurring group 1 as sexual host. Interestingly, the fourth distinct group appears to represent hybrid offspring of the two putative hybridogenetic lineages. The propagation of clonal haploid genomes by both males and females and the ability of these clones to unite and form sexually mature diploid hybrid offspring may represent a novel mechanism that contributes to the dynamics of coexistence between hybridogenetic lineages and their sexual hosts.

The Role of Translocation in Recovery of Woodland Caribou Populations - NICHOLAS J. DECESARE; JESSE WHITTINGTON; MARK HEBBLEWHITE; HUGH ROBINSON; MARK BRADLEY; LALENIA NEUFELD; MARCO MUSIANI (Conservation Biology, 2011)
Maintenance of viable populations of many endangered species will require conservation action in perpetuity. Efforts to conserve these species are more likely to be successful if their reliance on conservation actions is assessed at the population level. Woodland caribou ( Rangifer tarandus caribou ) were extirpated recently from Banff National Park, Canada, and translocations of caribou to Banff and neighboring Jasper National Park are being considered. We used population viability analysis to assess the relative need for and benefits from translocation of individuals among caribou populations. We measured stochastic growth rates and the probability of quasi extinction of four populations of woodland caribou with and without translocation. We used two vital rates in our analysis: mean adult female survival and mean number of calves per breeding‐age female as estimates of mean fecundity. We isolated process variance for each vital rate. Our results suggested the Tonquin caribou population in Jasper is likely to remain viable without translocation, but that translocation is probably insufficient to prevent eventual extirpation of the two other populations in Jasper. Simulated reintroductions of caribou into Banff resulted in a 53–98% probability of >8 females remaining after 20 years, which suggests translocation may be an effective recovery tool for some caribou populations.

Biosensor measurement of purine release from cerebellar cultures and slices - Mark Wall; Robert Eason; Nicholas Dale (Purinergic Signalling, 2010)

HvNax3—a locus controlling shoot sodium exclusion derived from wild barley (Hordeum vulgare ssp. spontaneum) - Yuri Shavrukov; Narendra K. Gupta; Junji Miyazaki; Manahil N. Baho; Kenneth J. Chalmers; Mark Tester; Peter Langridge; Nicholas C. Collins (Functional & Integrative Genomics, 2010)

A global synthesis of plant extinction rates in urban areas - Amy K. Hahs; Mark J. McDonnell; Michael A. McCarthy; Peter A. Vesk; Richard T. Corlett; Briony A. Norton; Steven E. Clemants; Richard P. Duncan; Ken Thompson; Mark W. Schwartz; Nicholas S. G. Williams (Ecology Letters, 2009)
Plant extinctions from urban areas are a growing threat to biodiversity worldwide. To minimize this threat, it is critical to understand what factors are influencing plant extinction rates. We compiled plant extinction rate data for 22 cities around the world. Two‐thirds of the variation in plant extinction rates was explained by a combination of the city’s historical development and the current proportion of native vegetation, with the former explaining the greatest variability. As a single variable, the amount of native vegetation remaining also influenced extinction rates, particularly in cities > 200 years old. Our study demonstrates that the legacies of landscape transformations by agrarian and urban development last for hundreds of years, and modern cities potentially carry a large extinction debt. This finding highlights the importance of preserving native vegetation in urban areas and the need for mitigation to minimize potential plant extinctions in the future.

Mortality in adult intensive care patients with severe systemic inflammatory response syndromes is strongly associated with the hypo-immune TNF −238A polymorphism - John V. Pappachan; Tim G. Coulson; Nicholas J. A. Child; David J. Markham; Sarah M. Nour; Mark C. K. Pulletz; Matthew J. Rose-Zerilli; Kim de Courcey-Golder; Sheila J. Barton; Ian A. Yang; John W. Holloway (Immunogenetics, 2009)

Blubber testosterone: A potential marker of male reproductive status in short‐beaked common dolphins - Nicholas M. Kellar; Marisa L. Trego; Corina I. Marks; Susan J. Chivers; Kerri Danil; Frederick I. Archer (Marine Mammal Science, 2009)
A novel molecular technique was used to measure blubber testosterone (BT) in 114 male short‐beaked common dolphins, Delphinus delphis , collected from incidental fishery bycatch and strandings. When these concentrations were compared across maturity states, the mean (± SEM) BT levels of mature D. delphis (14.3 ± 3.0 ng/g) were significantly higher than those of pubertal (2.5 ± 0.5 ng/g, P = 0.006) and immature animals (2.2 ± 0.3 ng/g, P P F = 5.39, P = 0.043). Conversely, we found no significant differences in BT concentration with respect to subepidermal depth ( F = 2.09, P = 0.146). Finally, testosterone levels in biopsies from 138 free‐swimming male D. delphis , of unknown maturity state, sampled off California were found to be of concentrations similar to those from the fishery bycatch and stranding samples and revealed an analogous trend with respect to ordinal date.

The effect of angiotensin-converting enzyme genotype on acute mountain sickness and summit success in trekkers attempting the summit of Mt. Kilimanjaro (5,895 m) - Nicholas S. Kalson; Julian Thompson; Andrew J. Davies; Suzy Stokes; Mark D. Earl; Adam Whitehead; Ian Tyrrell-Marsh; Hannah Frost; Hugh Montgomery (European Journal of Applied Physiology, 2009)

Survival in the Rockies of an endangered hybrid swarm from diverged caribou ( Rangifer tarandus ) lineages - ALLAN D. McDEVITT; STEFANO MARIANI; MARK HEBBLEWHITE; NICHOLAS J. DECESARE; LUIGI MORGANTINI; DALE SEIP; BYRON V. WECKWORTH; MARCO MUSIANI (Molecular Ecology, 2009)
In North America, caribou ( Rangifer tarandus ) experienced diversification in separate refugia before the last glacial maximum. Geographical isolation produced the barren‐ground caribou ( Rangifer tarandus groenlandicus ) with its distinctive migratory habits, and the woodland caribou ( Rangifer tarandus caribou ), which has sedentary behaviour and is now in danger of extinction. Herein we report on the phylogenetics, population structure, and migratory habits of caribou in the Canadian Rockies, utilizing molecular and spatial data for 223 individuals. Mitochondrial DNA analyses show the occurrence of two highly diverged lineages; the Beringian–Eurasian and North American lineages, while microsatellite data reveal that present‐day Rockies’ caribou populations have resulted from interbreeding between these diverged lineages. An ice‐free corridor at the end of the last glaciation likely allowed, for the first time, for barren‐ground caribou to migrate from the North and overlap with woodland caribou expanding from the South. The lack of correlation between nuclear and mitochondrial data may indicate that different environmental forces, which might also include human‐caused habitat loss and fragmentation, are currently reshaping the population structure of this postglacial hybrid swarm. Furthermore, spatial ecological data show evidence of pronounced migratory behaviour within the study area, and suggest that the probability of being migratory may be higher in individual caribou carrying a Beringian–Eurasian haplotype which is mainly associated with the barren‐ground subspecies. Overall, our analyses reveal an intriguing example of postglacial mixing of diverged lineages. In a landscape that is changing due to climatic and human‐mediated factors, an understanding of these dynamics, both past and present, is essential for management and conservation of these populations.

Independent colonization and extensive cryptic speciation of freshwater amphipods in the isolated groundwater springs of Australia's Great Artesian Basin - NICHOLAS P. MURPHY; MARK ADAMS; ANDREW D. AUSTIN (Molecular Ecology, 2009)
The groundwater‐dependent springs of the Great Artesian Basin (GAB) in arid inland Australia represent a unique and threatened ecosystem. These incredibly isolated springs support a diverse array of endemic flora and fauna. One of the common faunal groups in the GAB springs is the freshwater amphipods of the family Chiltoniidae. The morphological conservatism and taxonomic uncertainty associated with these amphipods has ensured their true biodiversity, phylogeographical history and evolutionary affinities have remained unknown. We have used mitochondrial DNA and allozyme data to unravel a complicated history of isolation, extinction and dispersal among spring amphipod populations across the GAB. The results provide evidence for multiple independent colonizations in the GAB springs, particularly within the Lake Eyre group of springs. The inclusion of a group of Western Australian (WA) stygobitic amphipods from populations up to 1500 km away found surprising evidence for a shared evolutionary history between stygobitic and GAB spring amphipods. Approximate dating of the diversity found between major clades suggests the majority of lineages originated in the late Miocene, around the time of the aridification of inland Australia. The large number of independent lineages and the close connection between GAB spring and WA stygobitic amphipods suggest that a significantly rich amphipod fauna existed in the much wetter environment that once existed in inland Australia. The results also provide evidence for a gross underestimation of the species diversity within the springs, with 12 putative species identified, a conclusion with significant implications for the ongoing conservation of the GAB springs.

Eutrophication and Consumer Control of New England Salt Marsh Primary Productivity - MARK D. BERTNESS; CAITLIN CRAIN; CHRISTINE HOLDREDGE; NICHOLAS SALA (Conservation Biology, 2008)
Although primary productivity in salt marshes is thought to be controlled by physical forces, recent evidence suggests that human disturbances can drive a switch to consumer control in these ecologically valuable ecosystems. We tested the hypothesis that nitrogen enrichment can trigger consumer control in salt marshes in Narragansett Bay, Rhode Island, with (1) a field experiment in which we manipulated nutrient availability (with nutrient additions) and insect herbivory (with insecticide application), (2) a survey of 20 salt marshes that examined the relationship between marsh nutrient status and herbivore pressure, and (3) insect herbivore removal at high and low nutrient input sites to directly test the hypothesis that nutrient enrichment is increasing insect herbivory in these marshes. Experimental nitrogen eutrophication initially increased plant productivity but eventually led to reduced plant biomass due to insect herbivory, and our surveys revealed that marsh nitrogen supply was a good predictor of herbivore damage to plants. Insects had minimal impacts on primary productivity in pristine marshes, but suppressed primary productivity in eutrophic salt marshes by 50–75%. Thus, eutrophication is currently triggering consumer suppression of primary productivity in New England salt marshes and may ultimately jeopardize the ecological and societal services these systems provide.

Combining DNA and morphological analyses of faecal samples improves insight into trophic interactions: a case study using a generalist predator - Ruth M. Casper; Simon N. Jarman; Nicholas J. Gales; Mark A. Hindell (Marine Biology, 2007)

Expression of signaling molecules associated with apoptosis in human ischemic stroke tissue - Nicholas Mitsios; John Gaffney; Jerzy Krupinski; Richard Mathias; Qiuyu Wang; Stuart Hayward; Francisco Rubio; Patricia Kumar; Shant Kumar; Mark Slevin (Cell Biochemistry and Biophysics, 2007)

Mapping the central effects of ketamine in the rat using pharmacological MRI - Clare L. Littlewood; Nicholas Jones; Michael J. O’Neill; Stephen N. Mitchell; Mark Tricklebank; Steven C. R. Williams (Psychopharmacology, 2006)

Intact automatic avoidance of obstacles in patients with visual form agnosia - Nichola J. Rice; Robert D. McIntosh; Igor Schindler; Mark Mon-Williams; Jean-François Démonet; A. David Milner (Experimental Brain Research, 2006)

Fecundity of banded wrasse (Notolabrus fucicola) from Otago, Southern New Zealand - Nicholas J. Harwood; P. Mark Lokman (New Zealand Journal of Marine and Freshwater Research, 2006)
To better understand the reproductive biology and to supply crucial data for fisheries management, fecundity of banded wrasse (Notolabrus fucicola) from Otago, southern New Zealand, was investigated over a 12‐month period from January 2004 to January 2005. The spawning season for banded wrasse from Otago was deduced to be from September through to December. The threshold diameter of oocytes undergoing germinal vesicle breakdown in vitro, therefore constituting a batch, was found to be c. 500 μ m. Batch fecundity was accordingly estimated at 74500 ± 34900 eggs/kg body weight. On the basis of cyclic changes in gonadosomatic index and levels of the sex steroids estradiol‐17β and 17α,20β‐dihydroxy‐4‐pregnen‐3‐one, it is likely that wrasse spawn once each lunar cycle during the spawning season, resulting in four batches of eggs each year around the time of the full moon. Calculated annual fecundity ranged between 298000 (± 139600) and 447000 (± 209400) eggs/ kg body weight. Notwithstanding inter‐annual and inter‐locational variation, these fecundity estimates provide a guideline for the management of banded wrasse.

Comparison of gene expression in segregating families identifies genes and genomic regions involved in a novel adaptation, zinc hyperaccumulation - VICTOR FILATOV; JOHN DOWDLE; NICHOLAS SMIRNOFF; BRIAN FORD‐LLOYD; H. JOHN NEWBURY; MARK R. MACNAIR (Molecular Ecology, 2006)
One of the challenges of comparative genomics is to identify specific genetic changes associated with the evolution of a novel adaptation or trait. We need to be able to disassociate the genes involved with a particular character from all the other genetic changes that take place as lineages diverge. Here we show that by comparing the transcriptional profile of segregating families with that of parent species differing in a novel trait, it is possible to narrow down substantially the list of potential target genes. In addition, by assuming synteny with a related model organism for which the complete genome sequence is available, it is possible to use the cosegregation of markers differing in transcription level to identify regions of the genome which probably contain quantitative trait loci (QTLs) for the character. This novel combination of genomics and classical genetics provides a very powerful tool to identify candidate genes. We use this methodology to investigate zinc hyperaccumulation in Arabidopsis halleri , the sister species to the model plant, Arabidopsis thaliana . We compare the transcriptional profile of A. halleri with that of its sister nonaccumulator species, Arabidopsis petraea , and between accumulator and nonaccumulator F 3 s derived from the cross between the two species. We identify eight genes which consistently show greater expression in accumulator phenotypes in both roots and shoots, including two metal transporter genes ( NRAMP3 and ZIP6 ), and cytoplasmic aconitase, a gene involved in iron homeostasis in mammals. We also show that there appear to be two QTLs for zinc accumulation, on chromosomes 3 and 7.

A comprehensive mouse IBD database for the efficient localization of quantitative trait loci - Alessandra C.L. Cervino; Mark Gosink; Mohammad Fallahi; Bruce Pascal; Christopher Mader; Nicholas F. Tsinoremas (Mammalian Genome, 2006)

Mapping the central effects of ketamine in the rat using pharmacological MRI - Clare L. Littlewood; Nicholas Jones; Michael J. O’Neill; Stephen N. Mitchell; Mark Tricklebank; Steven C. R. Williams (Psychopharmacology, 2006)

Mineralogical and chemical evolution of the Ernest Henry Fe oxide–Cu–Au ore system, Cloncurry district, northwest Queensland, Australia - Geordie Mark; Nicholas H. S. Oliver; Patrick J. Williams (Mineralium Deposita, 2006)

DETERMINING PREGNANCY FROM BLUBBER IN THREE SPECIES OF DELPHINIDS - Nicholas M. Kellar; Marisa L. Trego; Corina I. Marks; Andrew E. Dizon (Marine Mammal Science, 2006)
We quantified progesterone in 110 blubber samples from dolphins of known reproductive status in order to test the accuracy of a method to determine pregnancy status in wild cetaceans. The samples were collected from fishery‐bycaught delphinids of three species ( Delphinus delphis , Lissodelphis borealis , and Lagenorhynchus obliquidens ). We ascertained that blubber progesterone concentrations could clearly distinguish pregnant D. delphis (range 132–415 ng/g, mean 261 ng/g) from non‐pregnant mature and immature ones (range 0.92–48.2 ng/g, mean 15.2 ng/g). We found similar dramatic differences in L. borealis and L. obliquidens . These results were insensitive to various blubber sampling depths and anatomical sampling locations on the body, suggesting relative homogeneity of progesterone levels throughout the blubber. However, no trend was found in blubber progesterone concentration with fetal length, indicating that although blubber progesterone appears to distinguish pregnancy status, it is unlikely to differentiate pregnancy stage. Based on the findings presented here we suggest that this method, when coupled with projectile biopsy procedures, can be used to assess the pregnancy status of free‐ranging cetaceans and thus provide a new tool to determine pregnancy rates of wild populations.

Examining the neural targets of the AMPA receptor potentiator LY404187 in the rat brain using pharmacological magnetic resonance imaging - Nicholas Jones; Michael J. O’Neill; Mark Tricklebank; Vincenzo Libri; Steve C. R. Williams (Psychopharmacology, 2005)

Bacterial diversity in the bacterioneuston (sea surface microlayer): the bacterioneuston through the looking glass - Mark P. Franklin; Ian R. McDonald; David G. Bourne; Nicholas J. P. Owens; Robert C. Upstill‐Goddard; J. Colin Murrell (Environmental Microbiology, 2005)
Summary The bacterioneuston is defined as the community of bacteria present within the neuston or sea surface microlayer. Bacteria within this layer were sampled using a membrane filter technique and bacterial diversity was compared with that in the underlying pelagic coastal seawater using molecular ecological techniques. 16S rRNA gene libraries of ≈ 500 clones were constructed from both bacterioneuston and the pelagic water samples and representative clones from each library were sequenced for comparison of bacterial diversity. The bacterioneuston was found to have a significantly lower bacterial diversity than the pelagic seawater, with only nine clone types (ecotaxa) as opposed to 46 ecotaxa in the pelagic seawater library. Surprisingly, the bacterioneuston clone library was dominated by 16S rRNA gene sequences affiliated to two groups of organisms, Vibrio spp. which accounted for over 68% of clones and Pseudoalteromonas spp. accounting for 21% of the library. The dominance of these two 16S rRNA gene sequence types within the bacterioneuston clone library was confirmed in a subsequent gene probing experiment. 16S rRNA gene probes specific for these groups of bacteria were designed and used to probe new libraries of 1000 clones from both the bacterioneuston and pelagic seawater DNA samples. This revealed that 57% of clones from the bacterioneuston library hybridized to a Vibrio sp.‐specific 16S rRNA gene probe and 32% hybridized to a Pseudoalteromonas sp.‐specific 16S rRNA gene probe. In contrast, the pelagic seawater library resulted in only 13% and 8% of 16S rRNA gene clones hybridizing to the Vibrio sp. and Pseudoalteromonas sp. probes respectively. Results from this study suggest that the bacterioneuston contains a distinct population of bacteria and warrants further detailed study at the molecular level.

Transdermal Delivery of Insulin Using Microneedles in Vivo - Wijaya Martanto; Shawn P. Davis; Nicholas R. Holiday; Jenny Wang; Harvinder S. Gill; Mark R. Prausnitz (Pharmaceutical Research, 2004)

Incorporating Collateral Data in Conservation Biology - NICHOLAS A. LINACRE; ALLAN STEWART‐OATEN; MARK A. BURGMAN; PETER K. ADES (Conservation Biology, 2004)
Conservation biologists often need to set ecological modeling assumptions or estimate parameters from sparse data. In some cases this problem can be addressed by incorporating data from closely related species or from the same species at different sites (i.e., collateral data). Currently no structured methods exist for incorporating such information. An analogous problem in Actuarial science is to set premium rates in situations with little direct data on claim frequency or size. The rates are estimated using actuarial credibility theory, which incorporates collateral data with the direct data. actuarial credibility theory combined with the actuarial control cycle financial management process also provides an adaptive mechanism for updating assumptions. This theory may have some utility for ecologists wanting to incorporate collateral data in an adaptive management framework, a companion to approaches such as Bayesian updating. We describe the historical development of actuarial credibility theory from early ad hoc methods to empirical Bayes approaches. We explore some of the theory's strengths, such as relative simple formulae for incorporation collateral data, and we explore some of the theory's weaknesses, such as the use of the best linear approximation to the Bayes estimate. We illustrate potential applications of the theory using an example on the mortality rate of the Powerful Owl ( Ninox strenua).

Cy3B™: Improving the Performance of Cyanine Dyes - Michael Cooper; Andreas Ebner; Mark Briggs; Miles Burrows; Nicholas Gardner; Robert Richardson; Richard West (Journal of Fluorescence, 2004)

Loading amplification of radiation grafted polymers (crowns and lanterns) and their application in the solid-phase synthesis of hydantoin libraries - Sylvain Lebreton; Nicholas Newcombe; Mark Bradley (Molecular Diversity, 2003)

5-HT 2C receptor mediation of unconditioned escape behaviour in the unstable elevated exposed plus maze - Nicholas Jones; Mark Duxon; Sheila King (Psychopharmacology, 2002)

Ethopharmacological analysis of the unstable elevated exposed plus maze, a novel model of extreme anxiety: predictive validity and sensitivity to anxiogenic agents - Nicholas Jones; Mark Duxon; Sheila King (Psychopharmacology, 2002)

Gas space and oxygen exchange in roots of Avicennia marina (Forssk.) Vierh. var. australasica (Walp.) Moldenke ex N. C. Duke, the Grey Mangrove - William G. Allaway; Mark Curran; Lauren M. Hollington; Malcolm C. Ricketts; Nicholas J. Skelton (Wetlands Ecology and Management, 2001)

Excessive glucocorticoid exposure during late intrauterine development modulates the expression of cardiac uncoupling proteins in adult hypertensive male offspring - Maria Langdown; Nicholas Smith; Mary Sugden; Mark Holness (Pflügers Archiv - European Journal of Physiology, 2001)

Determination of trace elements in porcine brain by inductively coupled plasma-mass spectrometry, electrothermal atomic absorption spectrometry, and instrumental neutron activation analysis - Antonia E. Panayi; Nicholas M. Spyrou; Livio C. Ubertalli; Mark A. White; Peter Part (Biological Trace Element Research, 1999)

Fruiting of putative ectomycorrhizal fungi under blue gum ( Eucalyptus globulus ) plantations of different ages in Western Australia - Xianheng Lu; Nicholas Malajczuk; Mark Brundrett; B. Dell (Mycorrhiza, 1999)

Evidence that the low-affinity K+ transport system of Rhodobacter capsulatus is a uniporter. The effects of ammonium on the transporter - Paul Golby; Nicholas P. J. Cotton; Mark Carver; J. Baz Jackson (Archives of Microbiology, 1992)